High strength biomaterials
The method of extruding a mixture of water-soluble polymers and solvents into a solvent removal environment to form nanoporous biomaterials addresses the challenges of achieving high strength and biocompatibility in medical devices without chemical crosslinkers or radiation, resulting in materials that meet or exceed ISO standards.
Patent Information
- Application Number
- JP2018533797
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2015-12-22
- Filing Date
- 2016-12-22
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2036-12-22
AI Technical Summary
Existing biomaterials for medical devices lack the combination of high strength, biocompatibility, and blood compatibility, particularly when manufactured without chemical crosslinkers or radiation.
A method for producing hydrophilic nanoporous biomaterials by heating a mixture of water-soluble polymers and solvents above the melting point, extruding it into a solvent removal environment, and continuing solvent removal to form crosslinked matrices that become nanoporous solids with high Young's modulus and tensile strength.
The resulting biomaterials exhibit enhanced strength, biocompatibility, and blood compatibility, meeting or exceeding ISO standards for medical devices, and can be manufactured without the use of chemical crosslinkers or radiation.
Smart Images

Figure 0007665280000013 
Figure 0007665280000014 
Figure 0007665280000015
Abstract
Description
[Technical field]
[0001] This application relates to porous biomaterials, including high strength hydrophilic nanoporous biomaterials, for medical devices. Summary of the Invention
[0002] Disclosed herein are biomaterials useful for manufacturing medical devices. Materials and methods are provided herein for the manufacture of tough, smooth, biocompatible biomaterials for various medical device applications. New process techniques have been used to create biomaterials with superior properties such as strength and hemocompatibility. Included herein are methods for extrusion of hydrophilic polymers to create high-strength, hemocompatibility, nanoporous biomaterials or other materials. These methods can be performed without the use of chemical crosslinkers or radiation crosslinking.
[0003] One embodiment is a method for making a hydrophilic material, comprising heating a mixture comprising at least one water-soluble polymer and a solvent above the melting point of the polymer, forming a mixture, and passing the mixture through a solvent-removing environment. Extrusion is used to form the mixture, and the mixture is formed into a continuous porous solid as it passes through a die. Nanoporous solids can be produced that have a Young's modulus of at least 5 MPa at the equilibrium water content (EWC) of the porous solid. Extrusion can be used to form high aspect ratio, high strength materials, including tubing useful as catheters.
[0004] One embodiment is a polymeric material comprising a hydrophilic porous solid, the porous solid having a solids content of at least 33% w / w and a Young's modulus of at least 5 MPa at equilibrium water content (EWC). The material may be formed with a high aspect ratio, e.g., 10:1 or greater, including materials formed as catheters. [Brief description of the drawings]
[0005] [Figure 1] FIG. 1 is a schematic diagram of an extrusion apparatus for forming a continuous form having a cross-sectional side view of a bath. [Diagram 2] FIG. 2 is an enlarged view of a portion of the apparatus of FIG. 1, showing the die head in a perspective view from outside the bath. [Diagram 3] FIG. 3 is an enlarged view of a portion of the apparatus of FIG. 1, showing the die head mounted in a bath. [Figure 4] FIG. 4 is a longitudinal cross-sectional view of a portion of a continuous porous solid formed with the apparatus of FIG. [Diagram 5] FIG. 5 is a plot showing the stress-strain curve of a polymeric material. [Figure 6] FIG. 6 is a plot of tensile test data for a porous solid produced with the apparatus of FIG. [Figure 7] FIG. 7 is a scanning electron microscope image (SEM) of the surface of the porous solid. [Figure 8] FIG. 8 is an SEM of a cross section of the porous solid of FIG. [Figure 9] FIG. 9 is a plot of data for dehydration of porous solid catheters, with the y-axis being weight and the x-axis being time (min). [Figure 10] FIG. 10 is a plot of tensile test data for porous solids produced according to Example 4, with the higher molecular weight polymer (PVA67-99) providing a higher modulus and tensile strength than the lower molecular weight polymer (PVA28-99). [Figure 11]FIG. 11 is a plot of tensile test data for porous solids produced according to Example 4, showing that the highest polymer concentration (26%) provides the material with the greatest modulus and tensile strength versus the lower polymer concentrations (22% or 18%). [Figure 12A] FIG. 12A is a photograph of a control (Bard POWERPICC) porous solid incorporating a radiopaque agent. [Figure 12B] Figure 12B is a photograph of an unannealed porous solid incorporating 5.7 wt% bismuth subcarbonate radiopaque agent. [Figure 12C] Figure 12C is a photograph of a porous solid incorporating a radiopaque agent, 12.1 wt% bismuth carbonate, that has not been annealed. [Figure 12D] Figure 12D is a photograph of the annealed porous solid incorporating 12.1 wt% bismuth subcarbonate radiopaque agent. [Figure 12E] Figure 12E is a photograph of the annealed porous solid incorporating 5.7 wt. % bismuth subcarbonate radiopaque agent. [Figure 12F] Figure 12F is a photograph of a porous solid incorporating 4.2 wt% bismuth subcarbonate, a radiopaque agent. [Figure 13] FIG. 13 is a photograph of the first set of test samples described in Example 7. [Figure 14] FIG. 14 is a photograph of a second set of test samples described in Example 7. [Figure 15A] FIG. 15A is a scanning electron micrograph (SEM) of a width-wise cross-section of the extruded porous solid described in Example 8. [Figure 15B] FIG. 15B is a scanning electron micrograph (SEM) of a longitudinal section of the extruded porous solid described in Example 8. [Figure 16]16A-16D are SEMs of hydrophilic nanoporous materials prepared as described in Example 9 and are provided at various magnifications indicated by the scale bar. [Figure 17A] FIG. 17A is a plot of tensile test data for samples produced as described in Example 10. [Figure 17B] FIG. 17B is a plot of tensile test data for samples produced as described in Example 10. [Figure 18A] FIG. 18A is a plot of tensile data for various blends of the polymer described in Example 11, with the data shown in N / mm2. [Figure 18B] FIG. 18B is a plot of tensile data for various blends of the polymer described in Example 11, with the data shown in N / mm2. [Figure 19] FIG. 19 is a plot of tensile data for various blends of the polymer described in Example 12, with the data shown in N / mm2. [Figure 20A] FIG. 20A is a photograph of the PEG / PVA copolymer extrudate described in Example 12 showing the surface with a PEG molecular weight of 8k. [Figure 20B] FIG. 20B is a photograph of the PEG / PVA copolymer extrudate described in Example 12 showing the surface with a PEG molecular weight of 20k. [Figure 20C] FIG. 20C is a photograph of the PEG / PVA copolymer extrudate described in Example 12 showing the surface with a PEG molecular weight of 35K. [Figure 21A] FIG. 21A provides the results of the blood contact test described in Example 15 as a photographic plot of relative thrombus accumulation. [Figure 21B] FIG. 21B provides the results of the blood contact test described in Example 15 as photographs of the test samples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0006] Materials, methods and uses are described herein for biomaterials comprising medically acceptable porous solids. These materials can be produced as tough, high-strength materials with smooth, biocompatible surfaces. Nanoporous and microporous solids with particularly high Young's modulus and tensile strength are described herein. Nanoporous materials are solids that contain interconnected pores (or pores) with a diameter of up to 100 nm. Methods for producing hydrogels are also described. Hydrophilic polymers can be used to produce these various porous solids, such that hydrophilic solids are obtained. The water content of nanoporous or microporous solids can be high, e.g., 50% w / w, in EWC. The water content of hydrogels can in principle be high, e.g., up to 90% w / w. Porous solid materials can be used to produce various devices, including medical catheters and implants, with a significant reduction in the adsorption and / or adhesion of biological components to the surface.
[0007] The process for producing the material can include extrusion to create devices with high aspect ratios. One embodiment of the method for producing the material includes heating a mixture comprising at least one water-soluble polymer and a solvent to a temperature above the melting point of the polymer solution, forming the mixture in a solvent removal environment to produce a crosslinked matrix, and continuing to remove the solvent until the crosslinked matrix is a microporous or nanoporous solid material. Crosslinking can be performed while cooling the mixture and / or in the solvent removal environment.
[0008] (Extrusion of polymer materials) Various techniques are known for producing solid plastic materials. These traditionally involve the extrusion of a polymeric material through an opening under conditions that shape the polymeric material into a solid plastic as it passes through the opening. Typically, there is a heating phase to soften or melt the polymer, a shaping / forming phase where the polymer is in a flowable form and under some kind of constraint, and a cooling phase where the shaped / formed polymer is cooled to a temperature where it retains its shape. The plastic may change somewhat after passing through the opening, such as shrinking, solvent removal, or crosslinking, but upon solidification, its shape is fixed. Thermoplastics can be remelted. Some thermosetting resins form strong inter- and / or intra-chain bonds that are non-covalent crosslinks, and are referred to as physical crosslinks to distinguish them from covalent bonds. Thermosetting resins are irreversibly formed by covalent crosslinks. Examples of shaping processes are thermoforming, molding processes, and extrusion processes. The extrusion process typically involves forcing a polymeric material through a shaped die under pressure. Usually, pellets of the polymer are fed into a hopper into a screw extruder that compresses and melts the polymer as it is fed into the die. After passing through the opening in the die, the polymer is rapidly cooled and becomes a solid shape. Extrusion can also include a drawing process. A multitude of complex shapes can be formed in the extrusion process. A multitude of shapes include objects with one or more lumens, coatings, layered coatings, filaments, hollow contoured objects, objects with round, square or complex cross sections, and copolymeric extrusions that combine multiple polymers in an extruder or die.The term "die" is used broadly herein to encompass the opening through which the polymer passes in the extrusion process to form a solid, including a mandrel, a combination of dies, a die containing one or more of port hole dies, a die with multiple openings that cooperate to produce an extruded product, a die that cooperates with a core, a core tubing, a core wire, a die that cooperates with air or gas acting as a core, or slit dies. The core is useful to provide a lumen for the continuously extruded product and may be used temporarily for devices with hollow lumens, or permanently in the case of coated devices (e.g., coated wire). Almost any shape can be made with a die, as long as the shape made has a continuous profile. The term "continuous" is a technical term that refers to the theoretical production of an unlimited length of material, even though semi-continuous, intermittent, or other processes may be used.
[0009] The extrusion process usually involves heating a polymer and forcing it to flow through a die while at an elevated temperature so that it can be rapidly cooled to set a plastic shape. The choice of temperature and conditions depends on factors such as the chemical composition and molecular weight of the polymer, the melting temperature (Tm), the glass transition temperature (Tg), the presence of crosslinks, and the effect of solvents, if any, present. Tm indicates the transition between the crystalline or semi-crystalline phase and the liquid amorphous phase. Tg indicates the temperature at which an amorphous polymer transitions from a rubbery, viscous liquid to a brittle, glassy, amorphous solid upon cooling. Amorphous polymers have a Tg but do not have a specific melting point, Tm. Conventional extrusion processes generally involve treating the polymer at elevated temperatures (typically above 150° C.) while it is in the extruder.
[0010] Disclosed herein is a novel process that provides for the extrusion of high strength materials. Certain aspects of this process provide for one or more of removing solvent from the hydrophilic polymer-solvent mixture when the material is extruded, extruded at low temperature, or extruded into a solvent-removing environment, and further removal at a time after extrusion. Additionally, an annealing step may be included.
[0011] 1-4 show one embodiment of an apparatus for producing materials. The illustrated device 100 includes a syringe pump 102 that accepts at least one syringe 104, an optional heating jacket (not shown) for heating the syringe, a die head 106, a heating element 108 and power cable 109 that provide the necessary heat for the die head 106 (details not shown in FIG. 1), a dispensing spool 110 for a core tube 112, an intake spool 114 and motor (not shown) for the core tube, and a bus 116 for extrusion material 117 (the bus having temperature control for cooling or heating shown as a heat exchanger 118 comprising heat exchange pipes 120 in the bus 116). The die head 106 accepts the core tube 110 passing therethrough. A supply line 122 from the syringe to the die head 106 provides the supply to the device 100. The system of this embodiment may further include a metering station, a jacketed vessel for heating and mixing the solution for loading into the syringes, and a solvent removal environment for further drying the tubes after removal from the bath 116. The system may also have a heating station for thermally annealing the tubes or other extruded products as needed. A core tube made of PTFE is useful, and wire, air, non-solvent liquids, or other materials may be used for the core.
[0012] In use, by way of example, the polymer is heated in a suitable solvent in a jacketed vessel and placed into a syringe 104. One or more polymers may be present, and radiopaque agents or other additives may be added. One or more syringes may be used with the same or different mixtures. The syringe of polymer is heated to a predetermined temperature, below 80-95°C, and degassed prior to extrusion. The syringe 104 is attached to a syringe pump 102 having a wrap heater that maintains the temperature during extrusion. The core 112 is looped through a die head 106, for example a heated out-dwelling die head, and fed into an extrusion bath 116, attached to a puller wheel 114 driven by a motor. The temperature of the bath is controlled using a heat exchanger 118, such as a chiller. The extruded material is typically extruded at a temperature ranging from -30°C to 75°C. Other temperatures may be used, with 0°C being a generally useful temperature setting for extrusion. One skilled in the art will recognize that all ranges and values between the explicitly defined boundaries are contemplated, e.g., any of -30°C, -25°C, -20°C, -15°C, -10°C, -5°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C may be utilized as upper or lower limits. The motor speed of the puller wheel 114 may be controlled to adjust the outer diameter gauge size around the core 112. Adjustments to the die size, material feed rate, tubing core diameter, and puller speed, for example, serve to adjust the final tubing gauge in the embodiment in which a catheter is manufactured. The polymer feed rate may be adjusted, for example, by control of the syringe pump 102 in this embodiment. A connector 122 connects one or more syringes to the die head 106. Many pumps and other tools are known for controllably delivering polymer solutions. The apparatus and method can be adapted to the drawing process although alternative feeding processes are available.Through this disclosure, one skilled in the art can apply the principles in light of what is known about extrusion or other molding techniques to produce alternative processes and devices that achieve the same end product as described herein. Scaled-up aspects of this process may be adapted for use, for example, in a multi-zone screw extruder, with the solvent mixture fed through appropriate injectors or hoppers, and zones controlled to feed the cooled extrudate. Features such as syringe pumps may be replaced with appropriately metered and controlled liquid or solid polymer feed systems. This system has been used to produce a variety of porous solid products, such as a 6F catheter with the properties shown in Table 1. Samples were produced using 13% w / w 85 kDa PVA with either 0.1% w / w 450 k PAA or 1% w / w 20 k PVP-iodine. In all cases, samples were extruded into chilled ethanol at 0°C to 15°C, soaked in ethanol overnight, and dried. The samples were then annealed in glycerol at 120°C for 6 to 17 hours and then rehydrated before testing. For PVA-PAA and PVP-iodine, samples were made with an average outer diameter of 1.59 mm (5F), as well as average outer diameters of 1.86 mm and 2.01 mm after hydration in aqueous solution for several days. 6F catheters were made with PVA. The tensile strength of several formulations was evaluated at equilibrium water content (EWC) and showed that increased strength was readily obtained compared to the ISO-10555 standard requirements. These samples not only met but exceeded the ISO criteria (see Table 1). [Table 1]
[0013] The tensile results in Table 1 were obtained from one batch of samples. The minimum strength required by ISO 10555-1:2013 is 2.25 for catheters with OD between 1.14 and 1.82 mm and 3.37 lbs (15 N) for catheters with OD greater than 1.82 mm. The average strength of samples made using the final casting process (approximately 12 F) resulted in samples with tensile strengths 164% greater than the minimum required. Catheters can be graded using the French nomenclature, where F stands for inner diameter. Fukumori et al. (Open J. Organic Polymer Materials 3:110-116(2013)) reported a freeze-thaw process that produced a poly(vinyl alcohol) (PVA) material with a Young's modulus of 181 MPa, with a Young's modulus of approximately 5 MPa or greater requiring at least about three cycles in the samples tested. The process that produced these gels required multiple freeze-thaw cycles. The resulting material was tested in a dry state and does not correspond to the strength measured by EWC. Fukumori et al. report that the crystalline content of the material increases with the number of freeze-thaw cycles, and that the strength of the material is due to larger crystals that form as the freeze-thaw cycles proceed, which form excellent cross-links that increase the Tg of the material. The nature of these processes produces a dry material. Additionally, as described below, the freeze-thaw process produces macropores.
[0014] In contrast, the process herein does not use a freeze-thaw process and / or does not use a freeze process and / or does not use a melt process. Moreover, the process can be used to produce a solid porous material with little or no swelling at EWC, e.g., 0%-100% w / w swelling, even in the absence of a covalent crosslinker. Those skilled in the art will recognize that ranges and values between the explicitly stated boundaries are contemplated, e.g., 0, 5, 10, 15, 20, 25, 30, 40, 50, 60, 70, 80, 90, 95, 100% w / w can be utilized as upper or lower limits. Swelling is measured as % Swelling = 100 x (total weight at EWC dry weight) / dry weight, where dry weight is the weight of the material without moisture.
[0015] Figure 5 shows the different regions of the stress-strain curve of a polymeric material. There are three main regions: Young's modulus, strain hardening, and break point. Young's modulus is defined as the slope of the linear elasticity of the material (change in stress / change in strain). Strain hardening is defined as the strengthening of the material with deformation. The break point is the point of maximum elongation. Tensile load and travel were plotted for the PVA (5F) sample as shown in Figure 6. The shape of the load curve was representative of other samples that underwent tensile testing. The sharp initial slope and eventual leveling out of the elongation may indicate the viscoelastic properties of the extruded PVA, which indicates that the material undergoes strain hardening and eventually strain softening until break. This particular sample exhibited a travel of 115 mm (454% elongation) at a maximum tensile load of 14.9 N. Other samples prepared in the same manner with an average diameter of 2.03 (6.4F) have an average ultimate tensile strength of 24.6 N (5.52 lbs). This substantial increase in tensile strength with such a small increase in cross-sectional area indicates that catheters made with these materials will significantly exceed the minimum standard of ISO 10555. The extruded samples have horizontal orientation and alignment along the length of the samples (in the direction of extrusion) as supported by the SEM of the nanoporous material provided in FIG. 7. The orientation of the polymer chains was produced by the extrusion process. FIG. 8 is an SEM image of a cross section of the same material prepared according to Example 1A, showing pore sizes below 100 nm.
[0016] Qualitative observations of sample strength, radiopacity, and surface finish and symmetry are very good. Sample surfaces, while not substantially perfect, are free of imperfections. Results obtained with extrudates superior to the same components when used to make cast samples containing severe parting lines; no severe lines, bumps or other imperfections were observed. The extrusion process has been observed to be efficient and useful for producing tough, high tensile strength tubing with high aspect ratios that would not be possible using conventional molds. A drawing process similar to extrusion may be employed.
[0017] Example 1A describes a general method for extruding a porous solid. Surprisingly, this process was effective. A cold extrusion process was produced, with the die held on the extrusion side in a bath at only 13°C. The polymer is hydrophilic and viscous at low temperatures. Cold extrusion was effective in producing a very strong material with other good properties including smoothness, defect-freeness, and consistent pore size. Extrusion was achieved with a mixture of polymer in a solvent, including PVA in water, used in Example 1A. Extrusion into a solvent removal environment, which in this example was an alcohol bath, contributed to the desired properties. In general, it is useful to use one or more combinations of extrusion of a hydrophilic polymer into a solvent, cold extrusion, and extrusion into a bath that quickly removes the solvent from the extrudate. Additionally, additional solvent removal and / or annealing processes provide further utility for producing the desired porous solid.
[0018] The process of Example 1A produced a nanoporous solid. The requirements for nanoporous materials include high polymer concentrations, greater than about 10% w / w in the polymer-solvent mixture with a high level of crosslinking. Those skilled in the art will recognize that all ranges and values between the explicitly stated boundaries are contemplated, for example, any of 10, 12, 15, 16, 17, 18, 19, 20, 25, 30, 35, 40, 45, 50, 55, 60, 70, 80, 90, 95, 99% w / w of polymer by weight in the total weight of the polymer-solvent mixture can be used as upper or lower limits. The polymer should be substantially solvated, meaning a true solution or at least half of the polymer is dissolved and the remainder is at least suspended. Solvation of the polymer contributes to polymer chain alignment and crosslinking between polymers during extrusion. Without being bound to a particular theory, it is believed that a high concentration of the starting polymer-solvent mixture helps with this. It is also believed that possible chain alignment of the material as it passes through the die promotes more intrapolymer vs. interpolymer crosslinking. It is believed that the extrudate or other formed mixture entering a gas or liquid desolvation environment will further collapse the pore structure before the closely packed polymers are fully crosslinked, thereby improving chain proximity and further increasing crosslink density. It is useful to deposit the extruded or otherwise formed material directly into a solvent removal environment. Further solvent can be removed to collapse the material until a desired end point in structure and / or properties is reached. An annealing process can further contribute to strength.
[0019] On the other hand, freezing increases strength by forcing superconcentrated microregions to achieve chain proximity and improve crosslink density, but retain macroporosity due to the presence of ice crystals throughout the entire gel structure. Desolvation creates forced superconcentrated microregions, but these do not generate macropores. In contrast, gels pre-established before dehydration or freezing are inherent in the process formed with macropores. Furthermore, our studies show that such nanoporous solids have greater strength than macroporous materials.
[0020] Hydrogels can also be produced by using lower polymer concentrations in the polymer-solvent mixture, typically less than 10% w / w of polymer in the polymer-solvent mixture. One skilled in the art will recognize that all ranges and values between the explicitly stated boundaries are contemplated, for example, any of 2, 5, 7, 8, 9, 10% w / w of polymer by weight in the total weight of the polymer-solvent mixture can be used as upper or lower limits. Additionally or alternatively, the polymer-solvent mixture is not extruded into a solvent removal environment.
[0021] Microporous materials can be produced using process conditions intermediate between those of nanoporous solids and hydrogels. One embodiment is to prepare the material using conditions equivalent to the production of nanoporous materials, but to stop solvent removal before it reaches a nanoporous solid structure.
[0022] Extrusion of hydrophilic polymers in solvents, including PVA of Example 1A, is useful for producing high strength materials. The use of solvents in the starting material at extrusion is not common, at least not at the very least. Typically, extrusion uses solid materials that are heated to a flowable temperature, then extruded, and then cooled by various methods. For example, extrusion of pure PVA is believed to be possible. However, such extrusion lacks the polymer structure required to produce a porous solid, and instead behaves like a conventional plastic. According to theory of operation, pure PVA extrusion would lack the quality of hydrogen bonding that occurs in the aqueous ionic solvent state. The appropriate temperature to prepare PVA to be flowable in extrusion produces a poorly cohesive (or adsorbent, cohesive) material at the die head, such that continuous shapes are not formed. It has been difficult to form extruded PVA into high aspect shapes, such as tubes, and use them in extrusion processes. The viscosity of PVA and other hydrophilic polymers is high and difficult to penetrate into solution. It has been observed that a narrow working band in temperature, e.g., 85-95°C, is useful. Below about 85°C, the PVA could not truly melt and therefore did not become completely amorphous for extrusion. Above about 95°C, boiling and losses to evaporation rendered the process ineffective. These temperature ranges can be offset by raising the pressure above atmospheric, but pressurized systems are difficult to use and to scale. The method is usefully carried out at temperatures below the boiling point of the polymer-solvent material.
[0023] The cohesion of the flowing polymer-solvent mixture was weak as it exited the die. The use of a core to support the mixture in the mold helps to hold the shape in the die. This condition is in contrast to typical core extrusions used as coating processes, for example for coating wires in cell phone chargers. Typical processes that avoid the use of solvents or significant solvent concentration have relatively high cohesion exiting the die that can easily hold the tube, and do not rely on active bonds, such as hydrogen bonds in hydrophilic polymers, to form the solid material into a coherent shape as it exits the die.
[0024] It was useful to pass the formed polymer-solvent mixture through a solvent removal environment. In Example 1A, for example, the use of a cold ethanol bath is atypical compared to conventional extrusion. Most extrusions do not use bath temperatures below room temperature. Furthermore, the use of a solvent removal bath is typical compared to conventional processes, as the bath or other solvent removal environment helps to solidify the extruded material sufficiently to be stable and concentric to the core, otherwise the melt would become teardrop-shaped. Attempting to retrieve it at the end of the extrusion would destroy it since it is still molten. A conventional bath containing water causes the PVA or similar hydrophilic polymeric material to lose its shape by swelling, dissolving, or both. Example 1B shows a molding process that involves the preparation of a polymer-solvent mixture that is formed in a mold and then subjected to a solvent removal environment. These methods do not have the advantage of the chain alignment observed in extrusion. However, properly controlled temperature and solvent removal can produce materials with high strength and controlled pore structure.
[0025] Example 2 shows that this method is effective when a radiopaque agent is incorporated, barium sulfate being the material used in this case. In Example 3, the porous material lost moisture when exposed to air at ambient conditions (Figure 9), but retained the desired properties and can be effectively transported / stored in sealed packages or solutions, or left in the ambient environment for a reasonable storage period, or as may be required after the user unpackages for end use. Example 4 shows increasing strength (modulus and ultimate break) as the molecular weight of the hydrophilic polymer (PVA) increases from 140k to 190k (Table 3). Bismuth subcarbonate was used as the radiopaque agent. In the same example, increasing the concentration of the polymer in the polymer mixture used for extrusion showed an increase in strength towards the highest concentration compared to lower concentrations (Table 5 and Figures 10-11).
[0026] The porous solids are very smooth, can be used in a hydrated state, and can be conveniently bonded to other materials. For catheters, for example, extensions, luer locks, suture wings, etc. are useful. Example 5 shows that conventional processes are effective for bonding other materials to the porous material. Examples 6 and 7 show that the porous solids are suitable for radiopaque medical devices and have good burst strength in pressure tests. Contact drop tests (Example 8) show that various porous solids are hydrophilic (PVA test). SEM images (15A-15B, Example 8) are images of nanoporous solids. Example 9 shows nanoporous solids (Figures 16A-16D).
[0027] The observations of the test samples, without being limited to a particular theory, indicate that crosslinking within the material provided by the first hydrophilic polymer (PVA) increases through interaction with the chains of the second polymer (PAA or PEG) until the second polymer begins to form domains with itself in the material. This is believed to be due to the ability to incorporate higher molecular weight species of the second polymer (PAA or PEG) which provide additional material strength. The results indicate that extrusion of the copolymer is useful in the range of 0.1% to 10% w / w of the second polymer or less than 10% w / w of the first polymer, with a range of less than 5% w / w of the first polymer also being useful. One of skill in the art will recognize that all ranges and values between the explicitly stated boundaries are contemplated, e.g., any of 0.1, 0.2, 0.4, 0.5, 0.8, 1, 2, 3, 4, 5, 6, 8, 10% w / w can be utilized as upper or lower limits.
[0028] The effect of various salts on the properties of the porous solids was evaluated as described in Example 10 (FIGS. 17A-B). The salts were useful for manipulating the strength of the material. Without being limited to a particular theory, it is believed that the salts are part of the physical crosslinks and act as low molecular weight crosslinkers between the polymer chains. Monosodium phosphate resulted in the highest Young's modulus and phosphoric acid produced the highest tensile strength. Boric acid increased both Young's modulus and ultimate tensile stress, while citric acid and phosphoric acid were comparable to each other. Boric acid forms high strength crosslinks but is not a covalent crosslinker.
[0029] Further tensile tests were performed on co-extrudates with a concentration of a first hydrophilic polymer and a relatively low concentration of a second hydrophilic partner (Example 11). Figure 18A shows tensile tests of PVA blends with low concentrations of 450 kDa PAA (0.1, 0.4 or 4.0% w / w PAA, 16% w / w PVA, percents are w / w concentrations of polymer in solvent). PAA concentrations of 0.1-0.4% w / w had higher strengths, supporting the conclusions stated for Examples 9 and 10 above. Higher molecular weight (MW) PAA (3 million Da) was tested (Figure 18B). However, in general, they had only about half the strength of the lower MW PAA. The decrease in tensile strength with increasing PAA molecular weight may be due to a decrease in bonding and / or entanglement interactions between PVA and PAA with chains longer than 3 million MW. No significant differences in strength were observed when three different MW PEGs were blended with PVA (8k, 20k, 35k PEG) (Figures 19 and 20A-C, Example 12). A PVA porous plastic without a radiopaque agent was superior to the control catheter in terms of non-thrombogenicity (Example 13, Figures 21A-B).
[0030] An embodiment of the polymer blend includes at least one first hydrophilic polymer and at least one second hydrophilic polymer in a solvent that is extruded as described herein. Examples include one or more combinations of PVA, PAA, PEG, PVP, polyalkylenes, hydrophilic polymers, and combinations thereof. Example concentrations include at least one second hydrophilic polymer present at 1 part to 10,000 parts of the first hydrophilic polymer. One of skill in the art will recognize that all ranges and values between the explicitly defined boundaries are contemplated, for example, any of 1, 2, 10, 100, 1000, 1500, 2000, 2500, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10,000 parts can be utilized as upper or lower limits. Examples of concentrations of polymers in the polymer-solvent mixture include a first polymer present at a first concentration and one or more additional polymers present at a second concentration, where the first polymer concentration and the additional polymer concentration are independently selected from, for example, 0.1 to 99%, e.g., 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 25, 30, 33, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95% w / w. Additionally, non-hydrophilic polymers and / or non-hydrophilic blocks in the block polymer may be present, and the concentration of such polymers and / or such blocks is generally less than about 10% w / w, e.g., 0.1, 0.2, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10% w / w.
[0031] (Process systems and parameters for making materials) Provided herein are processes for producing biocompatible porous solids, such as microporous or nanoporous solid materials, that have low protein adsorption properties and provide the basis for non-biofouling devices. Modification of starting polymer concentration, molecular weight, solvent removal, forming process, and curing / annealing process may provide surface properties with reduced protein adsorption and other properties. Certain embodiments include extrusion of polymer mixtures to produce a variety of continuous shapes. The mixtures may be further cured and annealed. These processes can be used to produce strong and highly lubricious materials. Embodiments include polymer mixtures extruded into shapes with single or multiple lumens of various diameters and wall thicknesses.
[0032] An embodiment of the process for producing a nanoporous solid material comprises heating a mixture comprising a polymer and a solvent (polymer mixture), extruding the mixture into a solvent removal environment, and removing the solvent from the crosslinked matrix until a nanoporous solid is formed. Depending on the process, one or more of these actions may be combined. Additionally, it is useful to cool the mixture as it exits the die. Without being limited to a particular theory of operation, crosslinking the polymer while passing through the die initially forms a porous matrix that has gaps between the polymer strands but does not have a pore structure and is therefore not a true nanoporous solid. As the solvent is removed under appropriate conditions, the crosslinked structure becomes a nanoporous solid. When the polymer mixture is extruded through the die and the mixture is cooled, crosslinking begins. Crosslinking may continue as the solvent is removed. The transition to form a nanoporous material occurs when the solvent is removed and is generally considered to be complete or essentially (meaning 90% or more) complete at this stage. The resulting material may be further processed by annealing in the presence or absence of additional solvent or plasticizer. This process, as well as other extrusion or other forming processes and / or materials described herein, may not include one or more of covalent crosslinking agents, agents promoting covalent crosslinking, radiation to crosslink polymer chains, freezing, thawing, freeze-thaw cycles, one or more freeze-thaw cycles, ice crystal formation, foaming agents, surfactants, hydrophobic polymers, hydrophobic polymer segments, reinforcements, wires, braids, non-porous solids, and fibers.
[0033] Porous materials may be produced by an extrusion process that includes forcing the polymer mixture through a die and through a cooling environment. The cooling environment may further be a solvent removal environment, or a dehydrating environment if the solvent is water. The die may have a core therethrough such that the polymer mixture forms around the core. Additional solvent removal and / or annealing environments may be used.
[0034] The extrusion process of the polymer-solvent mixture may be carried out as cold extrusion. The term "cold extrusion" refers to a process that includes passing a polymer-solvent mixture through a die, without the need to heat the polymer-solvent mixture above its boiling point during the entire process of preparing and extruding the polymer-solvent mixture. Thus, in cold extrusion, the die head is kept below the boiling point of the polymer-solvent mixture. Although many solvents may be used, water is often a useful solvent, in which case the die head is kept below 100°C, although lower temperatures may be useful as described above. The term "polymeric mixture" refers to a polymer in solution, or dissolved or suspended in a solvent. The solvent may be, for example, water, an aqueous solution, or an organic solvent. Heating the polymer mixture may comprise heating the mixture to a temperature above the melting point of the polymer. Generally, a solution transitions from a cloudy state to a clear state when it reaches the melting point.
[0035] Extrusion is a useful process for forming the material. Other forming processes may be used, such as molding, casting, or thermoforming the polymer-solvent mixture. Generally, the polymer-solvent mixture is prepared without boiling and formed into a shape that is exposed to solvent removal conditions that are controlled to produce nanoporous or microporous materials using the guidelines provided herein. Annealing processes may also be included. Hydrogels that are not microporous or nanoporous may also be produced.
[0036] The heated polymer mixture may be molded or otherwise formed when it is cooled or molded / formed and immediately cooled. The term "formed" is a broad term that refers to the passing of material from an amorphous molten state to a final product or intermediate shape for further processing. Forming encompasses casting, lamination, coating, injection molding, stretching, and extrusion. Forming can be done with an injection molding device made of a material that has thermally conductive properties that allow it to be easily heated to enhance the flow of the injected polymer mixture and rapidly cooled in a cooling environment. In other aspects, the molding process can be accomplished by extruding the polymer mixture through a die to form a continuous material.
[0037] Cooling the polymer mixture may comprise cooling the extruded material, for example, as when passing the polymer material through a die. An embodiment for cooling is a liquid bath at a temperature at least 20°C below the boiling point of the polymer mixture or below the Tm of the polymer mixture, for example, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110°C, below the boiling point or Tm of the polymer, or a bath or other environment at a temperature between -50 and 30°C. One skilled in the art will recognize that all ranges and values between the explicitly stated boundaries are contemplated, for example, any of -50, -45, -25, -20, -10, -5, -4, 0, 15, 20, 25, 30°C may be utilized as upper or lower limits. Cooling may be performed in a solvent removal environment. Freezing temperatures may be avoided. Without being limited to a particular theory of operation, the polymer chains are cooled to a point that promotes crosslinking and locks in chain transfer. This can occur at temperatures above 30°C or even higher if time permits. The bath may be aqueous and may be osmotically adjusted with salts or other osmotic agents to effect solvent removal for aqueous materials at relatively low osmolarity values by osmosis and diffusion. The bath may be other solvents that freeze at lower temperatures than water, thereby allowing temperatures below 0°C to be used without freezing the solvent or material. When hydrophilic copolymers are used in combination with PVA, for example, temperatures above 20°C are used for crosslinking, with immobilization of the chains occurring at much higher temperatures.
[0038] A "solvent-removing environment" refers to an environment that significantly promotes the removal of the solvent compared to drying at ambient conditions. Such an environment may be unheated, meaning that it does not exceed ambient temperature, e.g., does not exceed 20°C. Such an environment may be a vacuum, e.g., a vacuum chamber, a salt bath, or a bath that removes the solvent in the polymer mixture. For example, the aqueous polymer mixture may be introduced into an ethanol bath, where ethanol replaces the water. The ethanol may then be removed. The salt bath may be, for example, a high salt concentration bath (1M to 6M). The process time in the solvent-removing environment and / or the cooling process may be independently selected to be 1 to 240 hours. A person skilled in the art will recognize that all ranges and values between the explicitly defined boundaries are contemplated, e.g., any of 1, 2, 5, 10, 24 hours, 1, 2, 5, 7, 10 days may be utilized as upper or lower limits. The salt may be a salt that dissociates to create singly, doubly, or triply charged ions.
[0039] One or more solvent removal environments may be used, or one environment may be adjusted in terms of temperature. Thus, a cooling bath may be used, followed by solvent removal in an oven or vacuum oven. A cleaning step may be performed before or after cooling or solvent removal, for example, by immersion in a series of solvents at different concentrations, different salt solutions, different proportions of ethanol or other solvents.
[0040] One embodiment is an extruded material that has undergone a solvent removal process that includes exposure to a salt bath, where the material is immersed in a series of diH2O baths (new or replaced baths) for a period of time (e.g., 2-48 hours, 4-24 hours) to remove excess salt from the cast material or end user device. The material is removed from the wash step and dehydrated to remove excess water. Dehydration can be accomplished, for example, using temperatures ranging from 20-60°C. Dehydration is generally accomplished at 37°C for 24 hours or more.
[0041] In one embodiment, the polymer mixture is extruded or otherwise formed, then exposed to a high salt concentration bath (1M-6M) for an inversely correlated period of time. The higher the salt, the shorter the time required for immersion. For example, immersion in a 6M solution of NaCl for 16-24 hours. After immersion, the material is not rinsed with a salt solution. The material is already strengthened and can be removed from any mold pieces carried over from the initial formation. Alternatively, after the salt or other bath, the material is immersed in a water bath and dehydrated to remove excess water. Dehydration can be done using temperatures ranging from 20-60°C. Dehydration can be done at 37°C for greater than 4 hours, greater than 24 hours, or in the range of 4 hours to 150 hours. One of skill in the art will recognize that all ranges and values between the explicitly stated boundaries are contemplated, e.g., any of 4, 6, 8, 10, 12, 16, 24, 48, 72, 96, 120, 144, 150 hours may be utilized as upper or lower limits. For example, dehydration at 40° C. for 6 to 24 hours has been observed to be useful.
[0042] In another embodiment, NaCl is incorporated into the starting polymer solution at a concentration ranging from 0.1 to 3M of the final polymer mixture volume. The polymer is dissolved in a heated solution under stirring and then brought above its melting point. Dry NaCl is slowly added to this solution under stirring until completely dissolved. The slightly cloudy solution is then drawn into a feed for the purpose of creating shapes via either injection molding, casting, extrusion and / or stretching. A quench is performed at the end of each process to rapidly reduce the temperature and form a solid material. In this embodiment, no additional salt soaks are required. After the material hardens, the material is removed from the molding process section, rinsed with water to remove salt, and dehydrated, if necessary.
[0043] The term "annealing" as used in the context of semicrystalline polymers or solid porous materials refers to heat treatment at an annealing temperature that corresponds to the melting temperature of the polymer in the nanoporous material. This temperature is usually lower than the melting temperature, within about 0-15% of the melting temperature. Plasticizers or other materials may affect the melting temperature, usually by pressing it. For example, for pure PVA, the annealing temperature would be within about 10% of the melting point of the PVA. If other materials are present, the annealing temperature will generally be lower. The theory of operation is that annealing is a process that is a relaxation of stress combined with an increase in the size of crystalline regions in the material being annealed. Unlike metals, annealing increases the strength of the annealed material. Annealing may be performed in one or more of air, gas, or in the absence of oxygen or water (e.g., in nitrogen, vacuum nitrogen, under argon, oxygen scavenger, etc.). For example, dehydrated PVA nanoporous materials have been tested by annealing. Annealing is used to increase the crystallinity of the PVA network, further reduce the pore size of the PVA network, and decrease the adsorption properties of the final gel surface. Annealing can be performed at temperatures ranging from 100 to 160°C, for example. In a preferred embodiment, this step is performed by immersing the dehydrated gel in a bath of mineral oil.
[0044] Annealing may be performed in gas or liquid at ambient, elevated or low (vacuum) pressure. The liquid may be a low molecular weight polymer (up to 2000 Da) or other material (e.g. mineral oil). Examples of low molecular weight polymers are glycerin, polyols, and polyethylene glycols below 500 MW. A useful embodiment is annealing in a bath of glycerin, for example at 140°C for 1-3 hours. The glycerin acts to further reduce the fouling properties of the gel by interaction and neutralization of the free hydroxyl end groups of the PVA network. The annealed nanoporous material is cooled, removed from the annealing bath, and rinsed from the bath medium using a series of extended immersions. The product is then dehydrated and conditioned for terminal sterilization.
[0045] Various types of dies may be used, including longitudinal, angular, transverse and helical extrusion heads, as well as single polymer extrusion heads used to extrude a single polymer and multi-layer extrusion heads used for the co-extrusion of multiple polymer layers or other layers. Continuous operation heads may be used as well as periodic ones. Various materials may be incorporated into or as layers, such as reinforcing materials, fibers, wires, braiding materials, braided wires, braided plastic fibers, and the like. Likewise, such materials may be excluded. Additionally, porous solids may be produced with specific properties, such as Young's modulus, tensile strength, solids content, polymer composition, porous structure or solvent content known and measurable to the exclusion of various other materials. Thus, embodiments include the materials disclosed herein described in terms of the properties of the material, regardless of various other incorporated materials. For example, a nanoporous solid has a known specific Young's modulus, even if the material has reinforcing wires that contribute additional strength. A core may be used with the extrusion die. The core may be air, water, liquid, solid, non-solvent or gas. Given this disclosure, one of ordinary skill in the art will appreciate that a variety of extrusion processes using these various types of cores may be useful. Cores made from polytetrafluoroethylene tubing (PTFE) are useful.
[0046] Multi lumen tubing has multiple channels running through its profile. These extrusions can be custom designed to suit device designs. Multi lumen tubing has variable outer diameters (Outer Diameter / OD), numerous custom inner diameters (Inner Diameters / ID's), and various wall thicknesses. This tubing comes in numerous shapes such as round, oval, triangular, square, and crescent. These lumens can be used for guidewires, fluids, gases, wires, and various other needs. The number of lumens in multi lumen tubing is limited only by the size of the OD. In certain embodiments, the OD can be as large as 0.5 inches, the ID can be as small as 0.002 inches, and the web and wall thickness can be as thin as 0.002 inches. Tight tolerances can be maintained to + / - 0.0005. One of ordinary skill in the art will recognize that all ranges and values between the explicitly defined boundaries are contemplated, e.g., any of 0.002, 0.003, 0.004, 0.007, 0.01, 0.02, 0.03, 0.04, 0.05, 0.1, 0.2, 0.3, 0.4, and 0.5 inches may be utilized as upper or lower limits for OD and / or ID. Tolerances may be, for example, 0.0005 to 0.1 inches. One of ordinary skill in the art will recognize that all ranges and values between the explicitly defined boundaries are contemplated, e.g., any of 0.0005, 0.001, 0.002, 0.003, 0.006, 0.01, 0.02, 0.03, 0.06, 0.8, 0.9, and 1 inch may be utilized as upper or lower limits.
[0047] Braided tubing can be made in a variety of configurations. For example, it can be braided using single or double wires, round or flat, as thin as 0.001 inches. A variety of materials can be used to manufacture braided tubing, including stainless steel, beryllium copper, and silver, as well as monofilament polymers. The braid can be wrapped with a variety of plastic insulated cables (pics) per inch over many thermoplastic substrates such as nylon or polyurethane. The advantage of a braided catheter shaft is its high torque capability and kink resistance. By modifying several factors during the braiding process, the properties of the tubing can be altered to meet performance requirements. After the braid is complete, a second extrusion can be applied to the top of the braided tube to encapsulate the braid and provide a smooth finish. Braided tubing can be obtained with walls as thin as 0.007 inches when required.
[0048] (Porous, Microporous and Nanoporous Materials) "Porous solid" is a term used broadly herein to refer to materials with a solid phase that contains large spaces, and is used to describe true porous materials and hydrogels with an open matrix structure. Some terms related to "porosity" are used somewhat loosely in the scientific literature, so it is useful to provide a specific definition here. The term "nanoporous material" or "nanoporous solid" is used herein to refer to solids made with interconnected pores having a pore size of up to about 100 nm in diameter. The term "diameter" is broad and encompasses pores of any shape, as is customary in these techniques. The term "microporous solid" or "microporous material" is used similarly herein to specifically refer to solids made with interconnected pores having a pore size of up to about 10 μm in diameter. These nano- or microporous materials are characterized by an interconnected porous structure. Some hydrogels, which those skilled in the art sometimes call hydrogel sponges, are true porous materials with a continuous and solid network material filled through the voids, the voids being the pores. However, the open matrix structure found in many hydrogels is not a true porous structure, and generally, for convenience, they are referred to as porous materials, or to use the analogy to pores when characterizing diffusion or other properties. For example, hydrogels are not nanoporous or microporous solids as those terms are used herein. The spaces between the strands of an open matrix hydrogel and those of the matrix are not interconnected pores. Hydrogels are crosslinked gels with solid-like properties that are not true solids, but because they are crosslinked, insoluble in solvents, and have significant mechanical strength, it is convenient for those skilled in the art to refer to them as solids. Hydrogels may have high water content, for example, 25% w / w at or above the EWC.Those skilled in the art of hydrogel technology use the term "porous" to characterize the net molecular weight cut off or to refer to the spacing between the strands of an open hydrogel matrix when the hydrogel does not have a true porous structure and is not a nanoporous or microporous material as used herein. The definitions of nanoporous and microporous materials as used herein are also in contrast to the statements that microporous materials are sometimes described as having pore diameters less than 2 nm, macroporous materials are described as having pore diameters greater than 50 nm, and the mesoporous category is somewhere in between.
[0049] The extrusion process for producing the materials of the present invention has several advantages. Extrusion has been observed to align the polymer in a parallel orientation that contributes to high tensile strength. The extruded and stretched polymer molecules align in the direction of the tube or fiber. The tendency to return to a random orientation is countered by the strong intermolecular forces between the molecules. In addition, extrusion provides for the creation of materials or devices with high aspect ratios compared to injection molding or other molding processes. In addition, extrusion provides good control of dimensions so that wall thickness, lumens or lumen placement can be controlled. The use of high concentrations of polymers above their melting point in a solvent has been useful to allow extrusion. Attempts to produce high strength materials with similar polymers have used other techniques that do not allow extrusion, are not efficient, and are often not suitable for producing practical end products.
[0050] For example, polyvinyl alcohol (PVA) was used herein to fabricate nanoporous materials with superior properties, especially compared to traditionally used PVA medical materials. Indeed, PVA is used extensively throughout the medical device industry and has an established track record of biocompatibility. PVA is a linear molecule with a rich history as a biocompatible biomaterial. PVA hydrogels and membranes have been developed for biomedical applications such as contact lenses, artificial pancreases, hemodialysis and synthetic vitreous humor, as well as implantable medical materials to replace cartilage and meniscus tissue. It is an attractive material for these applications due to its biocompatibility and low protein adsorption properties, resulting in low cell adhesion compared to other hydrogels.
[0051] Others have attempted to improve the properties of PVA for biomedical purposes. For example, freeze / thaw processes have been tested. Techniques for forming hydrogels from PVA, such as "salting out" gelation, have been shown to form useful polymer hydrogels using different molecular weights and concentrations. Manipulation of Flory interactions has also been investigated in the formation of PVA gels by combination of two solutions (U.S. Pat. No. 7,845,670; U.S. Pat. No. 8,637,063; U.S. Pat. No. 7,619,009) for the use of PVA as an injectable in situ forming gel to repair intervertebral discs. In general, conventional processes for producing tough PVA materials have been studied in U.S. Pat. No. 8,541,484. Methods for doing this without the use of radiation or chemical crosslinkers have also been previously investigated, as shown in U.S. Pat. No. 6,231,605. Other work related to this PVA did not result in the invention described herein. Some of these other materials were useful in terms of tensile strength, but were nevertheless macroporous in nature.
[0052] In contrast, the process herein provides high strength materials with true porous structures and other useful properties such as an unexpectedly good combination of good biocompatibility and mechanical properties. Porous solid material embodiments are provided that have a combination of structural features independently selected from pore size, tensile strength, Young's modulus, solids concentration, crosslinking type and degree, internal orientation, hydrophilicity, and material composition, and optionally end user devices or intermediate materials with desired aspect ratios having molded shapes, lumens, multiple lumens, tubes with concentrically arranged lumens or thickness tolerances, or specific medical devices, each of which is described in detail herein.
[0053] Embodiments include nanoporous materials having pore sizes less than or equal to 100 nm, or in the range of 10-100 nm. One of skill in the art will recognize that all ranges and values between the explicitly stated boundaries are contemplated, e.g., any of 1, 2, 3, 4, 5, 10, 20, 50, 60, 70, 80, 90, 100 nm can be used as upper or lower limits.
[0054] Embodiments include nanoporous or microporous materials having a tensile strength at break, as measured by EWC, of at least about 50 MPa or 1-300 MPa. One of skill in the art will recognize that all ranges and values between the explicitly stated boundaries are contemplated, and any of 10, 20, 30, 40, 50, 60, 70, 100, 200, 300 MPa can be used as upper or lower limits.
[0055] Embodiments include nanoporous or microporous materials having a Young's modulus, as measured by EWC, of at least about 1 MPa or between 1 and 100 MPa. One of skill in the art will recognize that all ranges and values between the explicitly stated boundaries are contemplated, e.g., any of 5, 10, 15, 20, 25, 30, 35, 40, 50, 60, 70, 80, 90, 100 MPa can be utilized as upper or lower limits.
[0056] Embodiments include nanoporous or microporous materials or hydrogels having an elongation at break, as measured by EWC, of at least about 100% or 50-500%. One of skill in the art will recognize that all ranges and values between the explicitly stated boundaries are contemplated, e.g., any of 50, 60, 70, 80, 90, 100, 200, 300, 400, 450, or 500% can be used as upper or lower limits.
[0057] Embodiments include nanoporous or microporous materials or hydrogels having at least 20% solids or 20-90% w / w solids as measured by EWC. One of skill in the art will recognize that all ranges and values between the explicitly stated boundaries are contemplated, e.g., any of 5, 10, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 80, 90% w / w% solids can be used as upper or lower limits. Percent solids are measured by comparing total weight at EWC to dry weight.
[0058] Tensile strength, modulus and elongation values may be mixed and matched in any combination within the ranges set forth in the guidelines of this disclosure.
[0059] Aspects include nanoporous or microporous materials or hydrogels with physical or covalent crosslinks or combinations thereof. The physical crosslinks are non-covalent, e.g., physical crosslinks are ionic, hydrogen, electrostatic, van der Waals forces, or hydrophobic packing. These materials may not contain covalent crosslinks, their covalent crosslinking products, and chemical products. Chemicals may be added during processing to create covalent crosslinks, as is known in the art of polymerization. Alternatively, the process and materials may not be the same.
[0060] Embodiments include hydrogels with nanoporous or microporous materials or internal alignment of polymer structures. Alignment may be visualized using SEM images in cross-section along the direction of extrusion (i.e., along the length of the tube). "Alignment" refers to the orientation of the majority of horizontal chains and along the length of the sample (in the direction of extrusion).
[0061] Embodiments include hydrogels having nanoporous or microporous materials or hydrophilic surfaces and / or hydrophilic materials. Materials made from polymers that are water-soluble are hydrophilic. A water-soluble polymer is a polymer that dissolves in water at a concentration of at least 1 g / 100 ml. A surface is hydrophilic if the contact angle of a water droplet on the surface is less than 90 degrees (contact angle is defined as the angle passing through the interior of the droplet). Embodiments include hydrophilic surfaces with contact angles between 90° and 0°. One skilled in the art will recognize that all ranges and values between the explicitly defined boundaries are contemplated, e.g., any of 90, 80, 70, 60, 50, 40, 30, 20, 10, 5, 2, 0° can be used as upper or lower limits.
[0062] Materials for use in the process and / or biomaterials may include polymers. Hydrophilic polymers are beneficial. For example, the one or more polymers may be selected from polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), polyethylene glycol (PEG), polyacrylic acid (PAA), polyacrylamide, hydroxypropylmethacrylamide, polyoxazolines, polyphosphates, polyphosphazenes, and polysaccharides, as well as variations of the same with added iodine (e.g., PVA-I, PVP-I) or variations with pendant groups, copolymers with one or more of PAA, PVA, PVP, or PEG, and combinations thereof. Two or more hydrophilic polymers may be mixed together to form a nanoporous material. The molecular weight of the polymer may affect the properties of the biomaterial. Higher molecular weights tend to increase strength, decrease pore size, and decrease protein adsorption. Thus, embodiments include polymers or hydrophilic polymers with a molecular weight of 40k to 5000k Daltons. One of ordinary skill in the art will recognize that all ranges and values between the explicitly stated boundaries are contemplated, e.g., any of the following molecular weights can be used as upper or lower limits: 40k, 50k, 100k, 125k, 150k, 250k, 400k, 500k, 600k, 750k, 800k, 900k, 1 million, 1.5 million, 2 million, 2.5 million, 3 million.
[0063] The term "PEG" refers to all polyethylene oxides, regardless of molecular weight or whether the polymer is hydroxyl terminated. Similarly, the terms "PVA", "PVP" and "PAA" are used without restriction with respect to terminal chemical moieties or MW ranges. Reference to polymers described herein includes all forms of polymers, including linear, branched, unactivated, and derivatized polymers. A branched polymer is a term that has a linear backbone and at least one branch, thus encompassing star, brush, comb, and combinations thereof. A derivatized polymer has a backbone that comprises the indicated repeat unit and one or more substituents or pendant groups, collectively referred to as derivatized moieties. "Substitution" refers to the replacement of one atom with another. A "pendant group" is a chemical moiety attached to a polymer, which may be the same or different from the polymer repeat unit. Thus, reference to a polymer includes highly derivatized polymers and polymers having less than 0.01-20% w / w of derivatized moieties (calculated as the total MW of the moiety compared to the total weight of the polymer). One of skill in the art will recognize that all ranges and values between the explicitly stated boundaries are contemplated, e.g., any of 0.01, 0.05, 0.1, 0.2, 0.3, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20% w / w can be utilized as upper or lower limits.
[0064] A porous solid may be formed as a monolithic material, as a layer on another material, device or surface, as multiple layers, or as one or more layers of material comprising nanoporous material. Thus, for example, multiple layers may be extruded and the layers may be independently selected to form one or more of a nanoporous material, a microporous material, a hydrogel, a single polymeric material, a material having two or more polymers, and a non-nanoporous material.
[0065] The process of making the material can also affect the material properties, including the concentration of polymer in the polymer mixture passing through the die. The starting concentration of PVA or other hydrophilic polymer can range, for example, from 5 to 70% by weight (w / w) in water, with about 10 to 30% (w / w) generally being preferred. One of skill in the art will recognize that all ranges and values between the explicitly defined boundaries are contemplated, and any of, for example, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70% can be utilized as upper or lower limits.
[0066] The processes described herein may be truncated at a point before the polymer is crosslinked and processed to become a true nanoporous material or adapted to avoid nanoporous structures. In general, such materials have lower strength and toughness and lower solids content. Such materials are generally hydrogels when hydrophilic polymers are used at relatively low solids. Thus, such materials, even hydrogels, are contemplated herein and may have somewhat lower properties compared to nanoporous materials, but may nevertheless produce materials superior to conventional processes and materials using the same polymers. Similarly, as a generalization, microporous solids will approach the properties of nanoporous materials and have strengths superior to those of hydrogels.
[0067] Embodiments include methods of making a polymeric material comprising heating a mixture comprising a water-soluble polymer and a solvent to a temperature above the melting point of the polymer, extruding the mixture, cooling the mixture while removing the solvent, and / or cooling while crosslinking. When multiple polymers are present in a solvent, the melting point of the combined polymer in the solvent, with or without other additives, can be readily determined by one of skill in the art by observing the mixture as it heats, for example, as the mixture goes from a cloudy to a noticeably translucent appearance. Additionally, some or all of the solvent may be removed from the mixture during cooling after or as part of a forming process using the mixture. Embodiments include removing at least 50% w / w of the solvent in less than 60 minutes (or less than 1, 2, 5, 10, or 30 minutes). Embodiments include removing at least 90% w / w (or at least 70% w / w or at least 80% w / w) of the solvent in less than 60 minutes (or less than 1, 2, 5, 10, or 30 minutes).
[0068] (product) With reference to the materials described herein, including nanoporous materials, microporous materials, and hydrogels, a final product or intermediate product or product including the material may be produced with a desired aspect ratio, for example at least 3:1. The aspect ratio increases as the length of the device increases and as the width decreases. Those skilled in the art will recognize that all ranges and values between the explicitly defined boundaries are contemplated, for example, any of 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 50:1, 100:1, 1000:1 may be utilized as upper or lower limits. High aspect ratios are highly advantageous for certain devices, for example, many types of catheters. In principle, thin tubes can be extruded continuously without any limit in terms of length. Such devices include, for example, tubes, rods, cylinders, and cross sections with square, polygonal, or circular profiles. One or more lumens may be provided in any of them. The device may be made of a single material, essentially a single material, or multiple materials including the various layers already described, or reinforcing materials, fibers, wires, braided materials, braided wires, braided plastic fibers.
[0069] In particular, the extrusion process provides for concentric placement of the lumens. Concentricity is in contrast to eccentricity, in the sense that the lumen is offset from the center. In the case of multiple lumens, the lumens may be positioned such that they are symmetrically positioned. Symmetry is in contrast to eccentric placement of the lumens, which is the result of a poorly controlled process. Aspects include the aforementioned devices having an aspect ratio of at least 3:1 with lumens positioned without eccentricity or one lumen concentric with the longitudinal axis of the device.
[0070] Porous solids, such as nanoporous materials, microporous materials, and strong hydrogels, may be used to fabricate catheters or medical textiles. Examples of catheters include central venous, peripheral central, midline, peripheral, tunneled, dialysis access, urinary, neurological, peritoneal, intra-aortic balloon pump, diagnostic, interventional, drug delivery, shunts, wound drains (external ventricular, intraperitoneal and intraperitoneal), and infusion ports. Porous solids may be used to fabricate implantable devices, either permanent or temporary, fully implantable and percutaneously implanted. The porous solid material may be used to fabricate devices that contact bodily fluids, including extracorporeal devices and / or intracorporeal devices, and including blood-contacting implants. Examples of such devices include drug delivery devices, (e.g., insulin pumps), tubing, contraceptive devices, feminine hygiene, endoscopes, grafts (including grafts with small diameters <6mm), pacemakers, implantable cardiovascular defibrillators, cardiac resynchronization devices, cardiovascular device leads, ventricular assist devices, catheters (cochlear implants, endotracheal tubes, tracheotomy tubes, drug delivery ports and tubing, implantable sensors (intravascular, transdermal, intracranial), ventilator pumps, and ophthalmic devices including drug delivery systems. Catheters can comprise tubular nanoporous material with fasteners that cooperate with other devices (e.g., Luer fasteners or fittings). Radiopaque agents may be added to the material, fiber, or device. The term "radiopaque agent" refers to agents commonly used in the medical device industry to add radiopacity to materials (e.g., barium sulfate, bismuth, or tungsten).
[0071] Medical fibers made from porous solids include applications such as sutures, threads, medical fibers, braids, meshes, knitted or woven meshes, nonwovens, and devices based thereon. The fibers are strong and flexible. Materials may be manufactured using these fibers to resist fatigue and wear.
[0072] (Further definitions) The term "medically acceptable" refers to a material that is highly purified, free of contaminants, and non-toxic. The term "consists essentially of" used in the context of a biomaterial or medical device refers to a material or device having less than 3% w / w of other materials or components, such 3% does not render the device unsuitable for the intended medical use. "Equilibrium water content" is a term that refers to the water content of a material when the wet weight of the hydrogel becomes constant and before the hydrogel degrades. Generally, materials with high solids content have been observed to reach equilibrium water content in 24-48 hours. Physiological saline refers to a phosphate buffer solution with a pH of 7-7.4 and a human physiological osmolality at 37°C. For the purposes of measuring equilibrium water content, distilled water is used. The term "w / v" means weight per volume, e.g., g / L or mg / mL. The terms "biomaterial" and "biomedical material" are used interchangeably herein and may be used in the biomedical field, such as implants, catheters, blood contacting materials, tissue contacting materials, diagnostic assays, medical kits, tissue sample processing or other medical purposes. Furthermore, while the materials are suitable for biomedical applications, they are not limited to the same and may be manufactured as general purpose materials.
[0073] The term "molecular weight / MW" is measured in g / mol. The MW of a polymer refers to the weight average MW unless otherwise stated. If the polymer is part of a porous solid, the term "MW" refers to the polymer before crosslinking. If the distance between crosslinks is specified, it is the weight average MW between the crosslinks unless otherwise indicated. The abbreviation "k" stands for thousands, M stands for "million," and "G" stands for billion, e.g., 50kMW means 50,000 MW. Dalton is also a unit of MW and similarly refers to the weight average when used for polymers.
[0074] All publications, journal articles, patents, and patent applications referenced herein are incorporated herein for all purposes, and the present specification controls in the event of conflict. Features of the embodiments described herein may be mixed and matched based on the needs of producing an operable process or product. EXAMPLES
[0075] Example 1A: Extrusion of PVA Porous Solid In the examples, the apparatus of Figure 1 is used when extrusion is described unless otherwise indicated. A 17 wt% PVA solution was prepared using 100 ml deionized water and 20 g PVA (85 kDa, Sigma-Aldrich). The water was heated (100°C) until the water began to boil, then the dry PVA was added slowly (over about 5-10 minutes) to the water with moderate mixing (mixer speed of about 40). A no-boil process is to prevent boiling by turning off the heat as soon as boiling begins. Once all the PVA was added and the solution began to thicken, the heat was reduced to about 90°C and the stirring speed was increased to ensure the polymer was completely dissolved and thoroughly blended. The PVA solution was stirred for about 2 hours. Upon completion, the solution was viscous and slightly opaque. The solution was poured into a 20 cc syringe and degassed in a 90°C oven. Heating / degassing usually does not exceed 2 hours.
[0076] The polymer samples were extruded using a PTFE monofilament pull speed of 7 (ARDUINO specific motor movement software, 84 mm diameter pulling wheel) into a bath of 13 °C ethanol (Fisher, 190 proof). After the sample was extruded, it was left to rest in the cold ethanol for approximately 30 minutes before being moved. The sample was then transferred to another container of ethanol and placed in a -25 °C freezer for 24 hours. The monofilament was then removed from the sample by clamping the end of the monofilament with tongs and slowly sliding the sample out. A mandrel slightly smaller than the inner diameter of the sample (0.033 inches) was inserted into the sample and the sample was allowed to dry flat in a 50 °C incubator for approximately 3 hours. After complete drying, the sample was annealed by immersing it in glycerol (Sigma-Aldrich) at 120 °C in a closed container for 24 hours ± 4 hours in an oven. After annealing, the sample was removed from the glycerol and gently rinsed with deionized water. The sample was then transferred to a new container of deionized water and allowed to rehydrate for approximately 24 hours. The sample can be dehydrated and rehydrated without any adverse effects or changes to the porous solid observed. This process produced a nanoporous solid material.
[0077] Example 1B: Molded PVA PVA gels were prepared by weighing 10 g of 85kMW PVA (88% hydrolyzed PVA) and adding it to 100 mL of diH2O under stirring heated to 80°C. The PVA was added slowly and mixed before increasing the temperature to 90°C. The PVA solution was stirred until clarity was achieved. Approximately 5 mL of the PVA solution was drawn into a syringe and degassed to remove trapped air. The PVA solution was poured into a preheated mold at 60°C and rapidly cooled using a refrigerated cooling source. The PVA gel was then removed from the mold intact on the mandrel.
[0078] The PVA gel was quenched in a 6M solution of NaCl. The PVA gel was soaked in the salt solution overnight (16-24 hours) and then removed. The hardened gel was then removed from the mandrel in a hydrated state to remove excess salt and soaked in diH2O for an additional 24 hours. The gel was then dehydrated to remove residual water by drying at 25°C for 24 hours.
[0079] Some of those gels were then annealed by immersing in mineral oil and heating at 140°C for 1 hour. The gels were rinsed thoroughly and submerged in oil to ensure that no parts were exposed. The gels were allowed to cool, rinsed with 20mL of diH2O, and then rehydrated with an additional 20mL of diH2O at 37°C. Other samples of gels were annealed by immersing in glycerin and heating at 120-130°C for 3-24 hours. The gels were rinsed thoroughly and submerged in glycerin to ensure that no parts were exposed to air. The gels were allowed to cool, rinsed with 20mL of diH2O, and then rehydrated with an additional 20mL of diH2O at 37°C.
[0080] Example 2: Extrusion of PVA-Barium A PVA-barium polymer solution was prepared using 100 ml of deionized water, 16 g of barium sulfate (Sigma-Aldrich), and 4 g of 85 kDa PVA (Sigma-Aldrich). The water was heated (100°C) until it began to boil. The dry barium sulfate was added slowly first and mixed until no clumps were observed for long. The dry PVA was then added slowly (over about 5 minutes) to the water with moderate mixing. Once all the PVA had been added and the solution began to thicken, the heat was reduced to about 90°C and the stirring speed was increased to ensure the polymer was completely dissolved and thoroughly blended. The PVA-barium solution was stirred vigorously for about 2 hours. Upon completion, the solution was viscous and white in color. The solution was poured into a 20 cc syringe and degassed in a 90°C oven. Typically, heating during degassing does not exceed 2 hours.
[0081] The sample was extruded in a manner similar to that described in Example 1 and then allowed to rest in cold ethanol for approximately 30 minutes before moving it. The sample was then transferred to another container of ethanol and placed in a freezer set at -25°C for 24 hours. The monofilament was then removed from the sample by clamping the end of the monofilament with tongs and slowly sliding the sample out. A mandrel slightly smaller than the inner diameter of the sample was inserted into the sample and the sample was allowed to dry flat in a 50°C incubator for approximately 3 hours. After complete drying, the sample was annealed by immersing it in glycerol (Sigma-Aldrich) at 120°C in a closed container for 24 hours ± 4 hours in an oven.
[0082] After annealing, the samples were removed from the glycerol and gently rinsed with deionized water. The samples were then transferred to a new container of deionized water and allowed to rehydrate for approximately 24 hours. Samples can be dehydrated and rehydrated without any adverse effects or changes being observed.
[0083] (Example 3: Rehydration rate / dehydration rate of PVA porous material) Over a 23 hour period, a percent loss of 55% was observed in a PVA sample prepared as described in Example 1A for a 3.5 French catheter. A plot of the weight loss over time in ambient air is shown in Table 2 below and in Figure 9. [Table 2]
[0084] Example 4: Tensile test example PVA extrusion samples were prepared by heating a slurry of 17.6 g of bismuth carbonate and 100 g of a 6.2 g / L monobasic sodium phosphate solution in a jacketed reactor at 95 °C and heating to temperature. To this, 25.8 g of PVA (Mowiol 28-99 or Sekisui Selvol 165, also known as 67-99) was added over 5 minutes while mixing at a 70% run setting (DITCV2 mixer). The polymer was mixed at 70% run setting for 1-1.5 hours. The polymer was degassed at 90 °C for less than 2 hours. The polymer was then extruded into 190 proof ethanol at 5 °C-10 °C and stored at ambient conditions for at least 30 minutes.
[0085] The polymer was dried at 55° C. for 3 hours and annealed in a forced convection oven at 140° C. for 1.5 hours. The samples were then rehydrated in 1×PBS at 37° C. for 2 hours.
[0086] Tensile strength (stress) was measured in Newtons on a Mark 10 tensile tester (Model DC4060) using a 100N digital force gauge (Model# M5-1006). Cross-sectional area was measured for samples using calipers (Mark 10 Model# 500-474) to measure outside diameter and a pin gauge set to measure inside diameter. PVA67-99 exhibits a nominal viscosity of 67 cP (nominal viscosity as a 4% solution in water) with 99% or greater hydrolysis. PVA28-99 exhibits a nominal viscosity of 28 cPs (nominal viscosity as a 4% solution in water) with 99% or greater hydrolysis. Viscosity of PVA is positively correlated with the molecular weight of the polymer. Table 3 and Figure 10 show the increase in Young's modulus and maximum tensile stress with increasing PVA viscosity. [Table 3]
[0087] An 18% PVA extrusion sample was prepared by heating a 100 g slurry of 17.6 g bismuth subcarbonate and 1.6 g monosodium phosphate solution in a jacketed reactor at 95 °C to temperature. To this, 25.8 g PVA (MOWIOL 28-99) was added over 5 minutes with mixing at 70% run setting (DITCV2 mixer).
[0088] A 22% PVA extrusion sample was prepared by heating a slurry of 23.3 g of bismuth subcarbonate and 100 g of a 6.2 g / L monosodium phosphate solution in a jacketed reactor at 95 °C until the temperature reached 95 °C. To this, 35.0 g of PVA (MOWIOL 28-99) was added over 5 minutes with mixing at 70% run setting (DITCV2 mixer).
[0089] A 26% PVA extrusion sample was prepared by heating a slurry of 35.4 g bismuth carbonate and 115.9 g of 6.2 g / L monosodium phosphate solution in a jacketed reactor at 95 °C until temperature reached 95 °C. To this, 53.2 g PVA (MOWIOL 28-99) was added over 5 minutes with mixing at 70% run setting (DITCV2 mixer).
[0090] Each set of polymers was mixed for 1.5-2 hours at 70% run setting. The polymers were degassed at 90° C. for less than 2 hours. The polymers were then extruded into 190 proof ethanol at 5° C.-10° C. and stored at ambient conditions for at least 30 minutes.
[0091] The polymer was dried in a vacuum oven at 40° C. for 24 hours and annealed in silicone oil at 140° C. for 1 hour. The samples were rinsed three times with 190 proof ethanol and then rehydrated in 1× PBS at 37° C. for 2 hours. The various preparations are described in Table 4. [Table 4]
[0092] The PVA in the mixtures in Table 4 was increased in the batch process relative to the monobasic salt solution. Increasing the PVA provided a higher ultimate tensile strength and Young's modulus. As the ratio of PVA to monobasic sodium phosphate is increased, stronger materials can be prepared. Figure 11 and Table 5 show that 26% PVA 28-99 has an increase in Young's modulus and ultimate tensile stress compared to 22% and 18% PVA 28-99. [Table 5]
[0093] Example 5: Attachment of extension tube / Luer lock to hydrogel The luer lock was attached to a polyurethane (PU) extension tube via cyanoacrylate. The extension tube was mated to the PVA catheter body by sliding the PVA catheter body approximately 0.5 inches. A heat gun was used at approximately 300° F., the PU / PVA was exposed 10 times with 0.5 second intervals and overlaps, repeated until infusion bonding of the PU and PVA occurred. Tensile data was evaluated on multiple samples. [Table 6]
[0094] Further testing showed that traditional ethylene-vinyl acetate (EVA) bonding processes for attaching extensions or other devices to catheters were effective for bonding such devices to extruded porous PVA material. Table 7 shows results where the attachment points exceeded PVA strength or otherwise exceeded all design requirements. A standard natural color EVA melt liner (OD: 3 / 16", wall: 0.014") and polyolefin RNF (heat shrink: 0.25") were used with PVA tubing (ID: 0.050" / OD: 0.063"-0.065") and luer hub (ID: 0.062" / OD: 0.101") with tubing assembly. A Steinel HG2310 LCD heat gun set at a temperature of 400°F (nozzle is 0.25 inch diameter, tip modified by compression to 0.12 inch width to provide a narrow heat zone area) and a 0.050 inch stainless steel mandrel was inserted through the luer hub / tube assembly into the ID of the PVA tubing.
[0095] Three samples using PE hub and PVA tube butt welds were fabricated at 400° F. The joints were observed to be very strong.
[0096] The clear luer hub and tubing assembly was slid into approximately 0.75 inch depth of PVA extrusion and an ethyl vinyl acetate melt liner and polyolefin were added to the assembly. The melt was produced and jointed at 400°F. Once the PVA extrusion and melt liner were melted, a more controlled shrinkage method was applied using gentle hand rolling of the melted joint to form a flat and prevent melting of the PVA tubing.
[0097] The PVA extrusion was inserted inside the hub and tube and bonded using the method described above. The strength was excellent. The assembly could not be pulled apart by hand. Two samples were made and used for hydration and testing. After conditioning in PBS at 37°C for 2 hours, the samples were tensile tested. The results are shown in Table 7. [Table 7]
[0098] Attachment of the suture wing overmold was also successful. EVA (Ateva 2803G with 20% bismuth subcarbonate) was used to injection mold the suture wings. A tension line (HTP Meds#2006-0335 Rev A) and PVA tubing were attached. A maximum break force (Wagner Instruments# FDK 30) of 27 N (6.1 lbf) was required to remove the PVA tubing and EVA suture wings. When the assembled PICC was hydrated, the break force was 28 N (6.2 lbf).
[0099] Example 6: Radiopacity Samples were prepared according to the method of Example 2. The samples are shown in Figures 12A-12F. The samples are a control (12A, BARD PowerPICC), unannealed 5.7 wt% bismuth subcarbonate (12B), unannealed 12.1 wt% bismuth carbonate (12C), annealed 12.1 wt% bismuth subcarbonate (12D), annealed 5.7 wt% bismuth subcarbonate (12E), and 4.2 wt% bismuth subcarbonate (12F).
[0100] All samples B-E exceeded the radiopacity of the control sample. The 4.2% bismuth subcarbonate sample (12F) exhibited approximately the same level of radiopacity or less, which is considered minimal for the sample. Radiopacity testing was performed at Mount Auburn Hospital in Cambridge, Massachusetts.
[0101] (Example 7: Power infusion) Pressure testing showed that the extruded porous plastic exceeded all design requirements. Power injection testing was performed on samples of the PVA-RO (radiopaque) agent incorporated nanoporous solids produced according to Example 2 using a Medrad MARK V PLUS POWER INJECTOR. The samples were attached to a barb / luer fitting with silicone tubing.
[0102] Water was injected at 5 mL / sec for 1 second and did not plug the sample (free flowing) and passed through the sample without breaking. Another identical sample of the same PVA-RO formulation was plugged and tested using the same parameters. The sample broke at the extension tube joint due to pre-existing damage from the heat shrink process.
[0103] Another set of samples, shown in Figure 13, were then attached to barbed fittings with Loctite 4902 and heat shrunk onto silicone tubing using the method described in Example 5. Barbs were attached to each end of the samples to allow for capping for occlusion testing. Samples 1 and 2 were tested using a flow rate of 5 ml / sec with a total liquid volume of 5 ML at 100 PSI. The samples broke near the heat shrink joint due to joint heat exposure (location of breakage shown in Figure 14).
[0104] Sample 3 was tested with reduced injection rates and volumes and passed two of three cycles with the following cycles: Cycle 1 used a flow rate of 0.4 mL / sec with 100 max PSI and a total volume of 1 mL, and Cycle 2 used the same parameters with 200 max PSI. Both cycles were completed. Cycle 3 used a flow rate of 5.0 mL / sec with 1 mL total volume and 350 max PSI. The tubing broke due to separation from the silicone and heat shrinking. No damage to the hydrogel was observed indicating that the PVA extruded tubing was able to withstand power injection when the proper attachment method (i.e., overmolding) was used.
[0105] Example 8: Contact angle Contact angle is measured for PVA-RO incorporating hydrogel made according to Example 2. A 1 cm section of the extruded material was cut from the main strand using a precision knife. The sample was then carefully cut along the length of the cross section. Loctite 406 is used to carefully adhere the sample to the glass slide. Once fully adhered, Loctite 406 is tapped along the edge of the sample and the wall of the sample is gently pressed onto the glass slide using forceps until it assumes a flat shape. A single droplet of colored water is placed on the surface of the material using a 20 μL pipettor. The droplet was immediately photographed and imported into an image viewer for measurement of the contact angle. All surfaces and the camera were leveled prior to testing. The sample had a contact angle of 60° as measured by the drop test (taken through the drop).
[0106] (Example 9: SEM Results) Also, Figures 15A-B are SEM images of a 17% PVA solution extruded using the method of Example 1A, except as otherwise specified. The sample was hydrated in distilled water at 37°C for 24 hours and then quickly frozen using liquid nitrogen to preserve the pore structure. The sample was then freeze-dried for 48 hours to remove the water and subjected to SEM analysis. Figure 15A shows a cross section of the extruded PVA tube, showing no macro-porosity in the gel structure. Figure 15B shows a longitudinal cross section of the extruded tube at higher magnification, showing no macro-porosity in the structure. This material has a high water content and is more porous, with pore sizes less than about 10 nm.
[0107] A sample of PVA extrudate was made by heating 200g of distilled water in a jacketed reactor at 95°C and heating to temperature. To this, 40g of PVA (Sigma, 146k-186k) was added over 5 minutes while mixing at 200 RPM. The polymer was mixed at 300 RPM for 1.5 hours. The polymer was degassed at 90°C for less than 2 hours. The polymer was then extruded into ethanol at -23°C using the apparatus of Figures 1-3. It was then stored in ethanol at -25°C in a freezer for 24 hours. The sample was dried for 6 hours. After drying, the sample was immersed in glycerol at 120°C for 17 hours. After annealing, the sample was removed, cooled and rinsed with ethanol. After rinsing, the core was removed. The sample was dried at 50°C for 12 hours. Two SEM images (Figures 16A-16D) show the results. 16C-16D are also taken at higher magnification, showing the nano-porosity.
[0108] Example 10: Salt Additive Various salts were used in the batch process, referring to the process of driving the polymer into solution in a polymer-solvent mixture, to vary the maximum tensile stress and Young's modulus. Multifunctional salts such as phosphoric acid, boric acid, and citric acid were used. These salts were added as sodium and / or potassium salts with various degrees of neutralization.
[0109] PBS (phosphate buffered saline) contains sodium chloride, potassium chloride and phosphate as major components. Three neutralization points are analyzed in comparison to PBS. 18% PVA (MW 146k-186k, Sigma-Aldrich #363065), 6% bismuth carbonate (Foster) (20 wt% based on solids) and mixtures of these phosphate solutions at constant molar ratios at 51.7 mM were tested with phosphoric acid (Sigma-Aldrich), monosodium (Sigma-Aldrich) and disodium phosphate (Sigma-Aldrich) in water. Monosodium phosphate yielded the highest Young's modulus and phosphoric acid yielded the highest tensile strength. Figure 17A is a plot of the tensile strength of 18% PVA samples formulated with PBS, monosodium phosphate, disodium phosphate and phosphoric acid. The effect of other multifunctional (two or more neutralization sites) salts was also evaluated and the results are plotted in Figure 17B. Boric acid (Sigma-Aldrich), citric acid (Sigma-Aldrich) and phosphoric acid (Sigma-Aldrich) are compared in 51.7 mM of each acid solution, 18% PVA (Sigma-Aldrich), 6% bismuth carbonate (Foster) (20 wt% based on solids). Boric acid increased both Young's modulus and maximum tensile stress, while citric and phosphoric acids were relatively the same.
[0110] Example 11: PVA and PAA Blended Batch and Copolymer Extrusion PVA-PAA blend solutions were batched using the following method (see Table 8 for formulation composition): 100 g of water and PVA were added to a high viscosity jacketed vessel heated to 90°C and mixed at 600 RPM. The bismuth subcarbonate concentrate was homogenized with the remaining water for 15 minutes, then 32 g of concentrate was added to the jacketed reaction vessel at 90°C unless otherwise noted. The PVA was then added to the vessel with mixing at 600 RPM. After 1 hour of mixing, the PAA was added to the solution and continued for 0.5 hours until the solution was completely homogenous. The polymer was then aliquoted into 20 mL syringes. [Table 8]
[0111] The polymer was reheated to 90° C. and degassed at 90° C. for 1 hour. The polymer was then extruded into ethanol at about 10° C. to about 21° C. The extrudate was left in the ethanol on the monofilament for about 0.5 hours. The extrudate was then transferred to room temperature ethanol and the monofilament was removed and allowed to dehydrate for 24 hours.
[0112] The extrudates were transferred to a vacuum oven and dried at 50°C for 48 hours. After drying, the samples were poured with USP grade mineral oil at 120°C and then immersed in mineral oil at 120°C in a convection oven for 2 hours. The samples were then removed from the mineral and cooled to room temperature. Rinsing / cleaning treatments were performed once with ethanol and twice with distilled water. The samples were transferred to PBS at 37°C to hydrate prior to tensile testing and surface evaluation. Tensile testing was performed according to ISO-10555 protocol. Tensile values are not normalized to the cross-sectional area of the samples.
[0113] Figure 18A is a comparison of PVA-PAA blend formulations with 450k molecular weight PAA. PAA formulations at 0.1% and 0.4% (w / w) concentrations in water extruded with 11-13% concentrations of PVA showed higher tensile strength than the 4.0% formulation. Higher water content correlates to an increased percentage of PAA and may reduce the strength between the PVA bonds and therefore the tensile strength. Furthermore, the 4.0%, 450k PAA formulation showed a spongy surface. Figure 18B is a comparison of PVA-PAA blend formulations with 3m molecular weight PAA. The 3m molecular weight PAA formulations at 0.3% and 0.4% (w / w relative to the solvent) showed higher tensile strength than the 0.2% formulation. The 3m molecular weight PAA-containing formulations showed approximately half the tensile strength values of the 450k PAA-containing formulations, except for 4.0%.
[0114] Example 12: Blended batches of PVA and PEG and copolymer extrusion PVA-PEG blend solutions were batched using the following method (see Table 9). The formulation composition was PVA (Sigma, 146k-186k), bismuth subcarbonate (Foster), 100g distilled water, and PEG8k (Sigma), PEG20k (Sigma) or PEG35k (Sigma). The bismuth subcarbonate was homogenized with water for 15 minutes and then added to a jacketed reaction vessel at 90°C. The PVA was then added to the vessel with mixing at 600 RPM for 2 hours. The PEG was then added to the solution and mixing was continued for 2 hours until the solution was completely homogenous. The polymer was then aliquoted into 20 mL syringes. [Table 9]
[0115] The polymer was reheated to 90° C. and extruded into ethanol at about 3° C. to 21° C. The extrudate was left in the ethanol on the monofilament for about 1 hour. The extrudate was then transferred to room temperature ethanol and the monofilament was removed and allowed to dehydrate for 24 hours.
[0116] The extrudates were transferred to a vacuum oven and dried at 50°C for 48 hours. After drying, the samples were poured with USP grade mineral oil at 120°C and then immersed in the mineral oil at 120°C for 2 hours in a convection oven. The samples were then removed from the mineral oil and cooled to room temperature. Rinsing / cleaning treatments were performed once with ethanol and twice with distilled water. Prior to tensile testing and surface evaluation, the samples were transferred to distilled water for hydration. Tensile testing was performed according to ISO-10555 protocol. Figure 19 shows the results and shows a comparison of PVA-1% PEG formulations of various MW PEGs (tensile values are not normalized to the cross-sectional area of the samples). The PEG blend extrudates yielded smooth surfaces, except for PEG35k, which formed a scale pattern along the outside of the extrudate. No significant differences were observed in the tensile strength of the 8k, 20k, and 35k PEG co-extrudates due to the large standard deviations of all 1% PEG blends. Figures 20A-C are images of 8k, 20k, and 35k PEG co-extrudates, respectively.
[0117] (Example 13: Evaluation of thrombus formation of PVA gel) A sample of PVA extrudate was made by heating 200g of distilled water to a temperature of 95°C in a jacketed reactor. To this, 40g of PVA (Sigma, 146k-186k) was added over 5 minutes while mixing at 200 RPM. The polymer was mixed at 300 RPM for 1.5 hours. The polymer was degassed at 90°C for less than 2 hours. The polymer was then extruded into ethanol at -23°C and then stored in ethanol in a -25°C freezer for 24 hours. The sample was dried for 6 hours.
[0118] After drying, the samples were immersed in glycerol at 120 °C for 17 h. After annealing, the samples were removed, cooled, and rinsed with ethanol. The cores were removed after rinsing. The samples were dried at 50 °C for 12 h.
[0119] A sample of PVA with barium sulfate was made by heating 50g of water in a jacketed reaction vessel at 90°C. In a side vessel, 4g of barium sulfate and 50g of water were homogenized at 11k RPM for 15 minutes and then added to the jacketed vessel. This was mixed and heated for 10 minutes. After heating, 16g of PVA (Sigma, 146k-186k) was added and mixed at 360 RPM for approximately 2 hours.
[0120] The PVA-RO polymer mixture was heated to 90°C and extruded into ethanol at -16°C. The extrudates were dehydrated at -25°C for 24 hours. The cores were removed and the samples were dried in an incubator at 50°C for approximately 6 hours. After drying, the samples were immersed in glycerol (Sigma) at 120°C for 17 hours. After annealing, the samples were removed, cooled and rinsed with distilled water. The samples were dried at 50°C for 12 hours and packaged for testing.
[0121] Samples were evaluated for antithrombotic durability testing at Thrombodyne, Inc. (Salt Lake City, UT). Each sample was cut to 15 cm in length with N=5 per sample group. Prior to testing, samples were sterilized using 12 hour ethylene oxide exposure. Samples were allowed to hydrate in distilled water for approximately 48 hours prior to evaluation, to represent clinical use.
[0122] Fresh heparinized bovine blood with autologous 111-labeled platelets was divided into test samples and a portion for control evaluation. Samples were inserted into an extracorporeal blood flow loop of 0.25 inch ID polyvinyl chloride tubing for approximately 120 minutes. Blood was kept at 98°C and pumped through the blood loop using a peristaltic pump for the duration of the test. After 45 minutes in the blood flow loop, samples were first checked for thrombus and removed after 120 minutes. At the end of the test, the devices were explanted from the tubing, rinsed with saline, and placed in a gamma counter for thrombus quantification. Test parameters are shown in Table 10. To allow for simultaneous comparisons without crossover effects, each test consisted of a separate flow system for each test sample and / or control circulating blood from the same animal.
[0123] Samples were measured for radioactivity and qualitatively assessed for the specific type of thrombus accumulation (i.e., adhesion or fibrin accumulation). Counting results are shown in Table 10. Percent thrombosis was calculated relative to the average total thrombosis observed in all test and control groups per animal blood cycled. The results of thrombus accumulation are shown in Tables 11-12 and Figure 21A. Visual assessment of thrombus formation is shown in Figure 21B for the commercial control catheter, the 17% PVA extrudate, and the 17% PVA-barium sulfate extrudate. [Table 10] [Table 11] [Table 12]
[0124] The results show a reduction in thrombus for the PVA formulation compared to commercial PICCs. The PVA-RO (barium as RO agent) formulation was not superior to the control group. Possible reasons include lack of micronization of barium and evidence of larger barium particles on the surface of the extrudate.
[0125] (Further Disclosure) 1. A method for producing a porous solid material comprising heating a mixture comprising at least one water-soluble polymer and a solvent to a temperature above the melting point of at least one polymer in the polymer-solvent mixture, cooling the mixture in a solvent removal environment to crosslink the polymers to produce a crosslinked matrix, and continuing to remove the solvent until the crosslinked matrix is a microporous or nanoporous solid material. 2. A method for producing a porous solid material comprising heating a mixture comprising at least one water-soluble polymer and a solvent to a temperature above the melting point of the last polymer in the mixture, forming the mixture (e.g., by molding or extrusion through a die), and passing the formed mixture through a solvent-removing environment. The method may further comprise one or more of, for example, cooling the mixture in the solvent-removing environment and continuing to remove the solvent until the crosslinked matrix is a nanoporous solid material or until it is a microporous solid material. 3. A method of making a porous polymeric material and / or a hydrophilic porous solid, comprising heating a mixture comprising at least one water-soluble polymer and a solvent to a temperature above the melting point of the polymer, forming a mixture (e.g., by extrusion through a die), and passing the formed mixture through a solvent removal environment. In the case of extrusion, a continuous porous solid is formed as the polymer passes through the die. An embodiment includes removing at least 50% w / w of the solvent in less than 60 minutes (or less than 1, 2, 5, or 10 minutes). An embodiment includes removing at least 90% w / w of the solvent in less than 60 minutes (or less than 1, 2, 5, or 10 minutes). The resulting material may be, for example, a hydrogel, a microporous material, or a nanoporous material. The extrusion may be cold extrusion. 4. The method of any of 1-3, wherein a salt is present in the mixture or added during the process. The salt may be useful in aiding in dissolving and / or crosslinking the polymer. The salt may be, for example, anionic, cationic, divalent, trivalent. Additionally, salts or other additives may be added to the polymer that may have two or more hydrogen-bond acceptors and / or hydrogen bond donor sites. 5. The method according to any of 1 to 4, wherein crosslinking occurs whilst cooling the mixture and / or in a solvent-removing environment. 6. The method of any one of 1 to 5, wherein the porous solid is crosslinked with bonds that are covalent bonds or physical crosslinks. These embodiments include the absence of covalent bonds when physical crosslinks are included. 7. The method of any one of 1 to 6, further comprising annealing the porous solid. 8. The method of any of 1 to 7, further comprising aligning the polymer chains of the continuous porous solid substantially parallel to one another. 9. The method of claim 8, wherein aligning the polymer chains comprises passing the mixture through a die. 10. The method according to any one of 1 to 9, wherein the at least one water-soluble polymer comprises PVA, PAA, PEG, PVP-I or PVP. 11. The method of any of 1-10, wherein at least one water-soluble polymer contains hydroxyl or carboxyl pendant groups. 12. The method of any of 1 to 11, wherein the mixture has at least one polymer in the mixture, the polymer being at a concentration of 5% to 50% w / w of the mixture. 13. The method of any one of 1 to 11, wherein the mixture has at least one polymer in the mixture at a concentration of 5% to 50% w / w of polymer to solvent. 14. The method according to claim 12, wherein at least 50% of the solid material forming the porous solid is PVA, PAA, PEG or PVP. 15. The method according to any one of 1 to 14, wherein the crosslinking is completed while the porous solid is in a solvent removal environment. 16. The method according to any one of 1 to 14, wherein the porous solid is prepared as a tube. 17. The method of any of 1-15, wherein exposure to the solvent removal environment removes at least half of the solvent in less than 60 minutes. 18. The method of any of 1-17, comprising exposure to a solvent-removing environment for at least 1 hour, e.g., exposure to a dehydrating environment for a period during which at least about 50% w / w of the total solvent is removed. 19. The method of any one of 1 to 18, wherein the porous solid has a Young's modulus at EWC of at least 5 MPa. 20. The method of any of 1 to 18, wherein the porous solid has, at EWC, an elongation at break of at least 200%, a Young's modulus of at least 5 MPa, and a tensile strength of at least 20 MPa. 21. The method of any one of 1 to 20, wherein the polymeric material further comprises a second material in contact with the porous solid, for example a second material which is a reinforcing material, a fiber, a wire or a plastic fiber. 22. The method of any one of 1 to 21, wherein the mixture comprises at least two polymers. 23A. The method of any of 1-22, wherein the at least one polymer comprises a first hydrophilic polymer and a second hydrophilic polymer, e.g., the first polymer and the second polymer are independently selected from PVA, PAA, PEG, PVP-I and PVP, and / or, e.g., the first polymer and the second polymer are present in a ratio of 1 part of the second polymer to 1-100,000 parts (w / w) of the first polymer. 23B. The method of any of 1-22, wherein at least one polymer comprises a first concentration of a first polymer and a second concentration of a second polymer, the first concentration being 10%-60% w / w and the second polymer being 1%-10% w / w, where w / w is the weight of polymer relative to the sum of the total weights of polymer and solvent in the mixture. 24. The method according to any one of 1 to 23, wherein the mixture further comprises a salt or other additive for crosslinking (23 refers to 23A and 23B). 25. The method according to any one of 1 to 24, further comprising an additive capable of having two or more hydrogen bond acceptor and / or hydrogen bond donor sites. 26. The method according to any of 22 to 25, wherein at least two polymers (e.g., two or more of polyvinylpyrrolidone, polyvinylpyrrolidone-iodine, polyethylene glycol and polyacrylic acid) are coextruded. 27. The method of claim 26, wherein the coextruded polymers are mixed at the die head. 28. The method of any of 22-26, wherein the water-soluble polymer is a first polymer formed as a first layer, and further comprises a second polymer formed as a second layer. 29. The method of any of 22-28, wherein the first polymer and the second polymer are coextruded as separate layers. 30. The method of any of 28-29, wherein the first polymer layer is formed as a sheet and the second polymer layer is formed in contact with the sheet. 31. The method of any one of 1 to 31, further comprising adding a third polymer. 32. The method of claim 31, wherein the third polymer is polyvinylpyrrolidone, polyvinylpyrrolidone-iodine, PEG, or polyacrylic acid. 33. The method of any of 21 to 32, wherein the second material is at least part of a reinforcing material, a fiber, a wire, a braiding material, a braided wire, a braided plastic fiber or a connector. 34. The method of any of 21 to 32, comprising a second material or polymer provided as a layer on or in the material. 35. The method of any of 21-34, wherein the second polymer or second material comprises polyethylene glycol or a polyol (e.g., the polyol is a polymer having at least three hydroxyl groups or the polyol is glycerin). 36. The method of any one of 1 to 35, further comprising adding a brazing material in contact with the porous solid. 37. The method of any one of 1 to 36, wherein preparing the mixture comprises adding PVA to a solvent. 38. The method of any of 1-37, wherein the solvent comprises (or consists essentially of) water, an alcohol, ethanol, a water-miscible organic solvent, or a combination thereof. 39. The method according to any one of 1 to 38, wherein the heated solvent is at a temperature of 70 to 120°C. 40. A method according to any one of 1 to 39, wherein the PVA concentration in the mixture is 15% to 25% w / w. 41. The process of any of 1 to 40, comprising cooling the mixture after or as it is formed, and passing the mixture through a cooling bath, a chilled mould, a frozen mould or liquid nitrogen. 42. The method of any of 1-41, wherein the solvent removal environment is a chamber filled with a gas, such as dry air or nitrogen or a gas at subatmospheric pressure, for example. 43. A method according to any one of 1 to 41, wherein the solvent removal environment is a solution comprising ethanol or a polyol. 44. The method of any of 1 to 41, wherein the solvent removal environment comprises a solution having an osmotic pressure that exceeds the osmotic pressure of the mixture. 45. The method of any of 1 to 44, wherein the solvent removal environment or solution comprises a salt present in a concentration of at least 0.1 molar. 46. The method of any of claims 44 to 41, wherein the solvent removal environment or solution comprises a salt present at a concentration in the range of 0.1 to 8 molar. 47. The method of any of 1-43, wherein the solvent removal environment or solution further comprises an osmotic agent, such environment having an osmotic pressure greater than the osmotic pressure of the mixture formed. 48. The method of any of 1 to 47, wherein the solvent removal process is carried out for a period of 3 to 48 hours. 49. The method according to any of 1 to 48, wherein the solvent removal process is carried out while the polymer is crosslinking. 50. The method of claim 49, wherein crosslinking is completed before the solvent removal process is completed. 51. The method of any of 1 to 50, further comprising an annealing process comprising heating the porous solid material to an annealing temperature. 52. The method according to claim 51, wherein the annealing temperature is 90 to 250°C. 53. A method according to any one of 51 to 52, wherein the annealing is carried out in the absence of air and / or oxygen and / or water. 54. A method according to any one of 50 to 53, wherein annealing is carried out at least partially in a liquid bath. 55. The method of claim 54, wherein the liquid bath comprises mineral oil and / or polyol and / or glycerin. 56. A method according to any one of claims 50 to 55, wherein annealing is carried out for a period of 3 hours to 1 week. 57. The method of any one of 1 to 56, wherein the mixture is passed through a die. 58. The method of claim 57, wherein the mixture is formed as a tube having at least one lumen. 59. The method of claim 57, wherein the tube is formed around the core. 60. The method according to claim 59, wherein the core is air, water, liquid, solid or gas. 61. The method of any of 57-60, further comprising extruding a second material or polymer as a layer into or within the crosslinked matrix. 62. The method of any of 57-61, wherein the mixture is a first mixture, the method further comprises a second mixture comprising a further material, and the second mixture is also passed through an extrusion die to form a second tubular layer. 63. The method of claim 61, wherein the second material is or comprises a reinforcing material, a fiber, a wire or a plastic fiber. 64. Any of the methods of 57-63, wherein the solid material surrounds the core and is confined within the tubular hydrogel layer or, if present, the second tubular layer. 65. The method of claim 64, wherein the solid material comprises a wire, a braid, a metal wire, a plastic wire, a metal braid, a plastic braid, a mesh, a fabric mesh, a metal mesh, or a plastic mesh. 66. The method of any of 1 to 65, wherein the porous solid is formed as a continuous form, a tube, a sheet, a solid cylinder, a tube or a ring having multiple lumens. 67. The method of any of 1-66, wherein the porous material has an aspect ratio of at least 4:1 (length:diameter), alternatively an aspect ratio of 3:1 to 100:1. 68. A method according to any one of 1 to 67, wherein the porous material is hydrophilic. 69. A catheter comprising a biocompatible material, a polymeric material, or a medically acceptable hydrophilic porous solid. 70. A catheter comprising a biocompatible material, polymeric material or porous polymeric solid having a tensile strength of at least 20 MPa, a Young's modulus of at least 5 MPa, a solids content of 10%-50% w / w at EWC, a solids content of at least 10% w / w or at least 33% w / w at EWC, a solids content of 10, 20, 30, 33, 35, 40, 50, 60% w / w at EWC, e.g., a polymeric material comprising a hydrophilic porous solid having a solids content of at least 33% w / w at equilibrium water content (EWC), and a porous solid having a Young's modulus of at least 5 MPa, and formed with an aspect ratio of, e.g., at least 10:1. For example, a polymeric material, wherein the porous solid comprises at least one polymer, the at least one polymer comprises a first hydrophilic polymer and a second hydrophilic polymer, the second hydrophilic polymer being present in an amount of 1 part to 1000 parts per 10,000 parts of the first polymer. 71. The biomaterial according to claim 69 or 70, wherein the porous polymer solid comprises a crosslinked hydrophilic polymer. 72. A biomaterial according to claim 70 or 71, having a porous polymer solid having a solids content of at least 33% w / w at equilibrium water content (EWC) in saline at 37°C, or alternatively a solids content of at least 50% w / w or in the range of 40% to 99% w / w. 73. A biomaterial according to any one of 70 to 72, wherein the solids content of the nanoporous material in the EWC is at least 50% w / w and the nanoporous material has a tensile strength of at least 20 MPa and / or a Young's modulus of at least 5 MPa. 74. A biomaterial according to any one of 70 to 73, having a pore diameter of 100 nm or less. 75. A biomaterial according to any of 70 to 74, having internal alignment of the polymer structure. 76. A biomaterial according to any of 70 to 75, having a PVA content of at least 50% w / w of the hydrogel at the EWC and a porous material which swells less than 50% w / w at the EWC when placed in an excess of saline and allowed to freely expand. 77. A biomaterial according to any of 70 to 76, which is a nanoporous or microporous material comprising or consisting essentially of at least one hydrophilic polymer, PVA, PAA, PEG or PVP or a combination thereof. 78. A biomaterial according to any one of 70 to 77, wherein the porous material comprises a matrix of a cross-linked hydrophilic polymer, the water-soluble polymer comprising hydroxyl and / or carboxyl pendant groups. 79. A biomaterial according to any one of 70 to 78, wherein the porous material comprises a crosslinked polymer having a molecular weight before crosslinking of at least 50 kg / mol, or a molecular weight (g / mol) of 50 k to 1000 k. 80. A biomaterial according to any one of 70 to 79, wherein at least 50% of the solid material forming the porous material is PVA, PAA, PEG or PVP. 81. A biomaterial according to any one of 70 to 80, wherein the porous material is crosslinked with covalent crosslinks or does not contain covalent crosslinks and / or does not contain a covalent crosslinking agent. 82. A biomaterial according to any one of 70 to 81, wherein the nanoporous material is crosslinked by physical crosslinking. 83. The biomaterial according to 82, wherein the physical crosslinks are ionic bonds, hydrogen bonds, electrostatic bonds, van der Waals forces or hydrophobic packing. 84. A biomaterial according to any one of 70 to 83, further comprising a layer of a second material or second polymer. 85. A biomaterial according to any one of 70 to 83, further comprising a second material encapsulated within the porous solid. 86. The biomaterial of claim 85, wherein the second material is at least a part of a reinforcement material, fiber, wire, braid material, braided wire, braided plastic fiber or connector. 87. A biomaterial according to any of 84 to 86, wherein the coating or layer of the second material or the second polymer comprises polyethylene glycol or a polyol (e.g., the polyol is a polymer having at least three hydroxyl groups, or the polyol is glycerin). 88. A biomaterial according to any of 84 to 87, wherein the coating or layer of the second material or the second polymer comprises PVA, PAA, PEG or PVP. 89. A biomaterial according to any of 70 to 88, further comprising a radiopaque (RO) agent, which may be, for example, a coating, layer on or in the biomaterial. 90. A biomaterial according to any one of 70 to 83, which consists essentially of PVA or the porous material consists essentially of PVA. 91. The biomaterial according to any one of 70 to 91, having a tubular shape. 92. A biomedical catheter comprising any one of the biological materials of 70 to 92. 93. The catheter according to 92, which is a central venous catheter, a peripherally inserted central venous catheter (PICC), a tunneled catheter, a dialysis catheter, a central venous catheter, a peripheral central venous catheter, a midline catheter, a peripheral catheter, a tunneled catheter, a dialysis access catheter, a urinary catheter, a neurocatheter, an intraperitoneal catheter, an intra-aortic balloon pump catheter, a diagnostic catheter, an interventional catheter or a drug delivery catheter. 94. A catheter described in any one of 92 to 93, comprising multiple lumens. 95. A biomedical catheter comprising a medically acceptable material, such as any of the materials of 1 to 94 (e.g., a hydrophilic nanoporous material, a hydrophilic microporous material, or a hydrogel).
[0126] This application claims priority to U.S. Provisional Application No. 62 / 271,150, filed December 22, 2015, which is incorporated by reference in its entirety.
Claims
1. 1. A method for manufacturing a catheter comprising a polymeric material, comprising: The manufacturing method includes: preparing a polymer mixture comprising at least one water soluble polymer and a solvent, said polymer mixture having a concentration of at least 10% w / w of said at least one water soluble polymer; heating the prepared polymer mixture so that the polymer in the mixture dissolves in the solvent to obtain a polymer mixture in which the polymer is dissolved; extruding the molten polymer mixture through a die as a tube; removing the solvent from the tube at a temperature above the freezing temperature of the solvent until the tube becomes a porous solid. Consisting of the tube being a porous solid comprising at least one water-soluble polymer; the porous solid tube is produced in the absence of a covalent crosslinking agent that forms covalent crosslinks between the extruded polymer to produce a porous solid; the porous solid tubes contain interconnected pores with pore sizes up to 100 nm in diameter and have a Young's modulus of 5-100 MPa at equilibrium water content (EWC); the at least one water soluble polymer is selected from polyvinyl alcohol (PVA), blends of PVA and polyethylene glycol (PEG), and blends of PVA and polyacrylic acid (PAA); The solvent comprises water, an aqueous solution or an organic solvent; The method, wherein the catheter comprises a porous solid tube.
2. 10. The method of claim 1, wherein the at least one water soluble polymer comprises poly(vinyl alcohol) (PVA), the PVA providing at least 50% w / w of the solids content of the porous solid.
3. 3. The method of claim 1 or 2, wherein the porous solid is a hydrophilic nanoporous solid, the pores of which have a size of 100 nm or less.
4. A method according to any preceding claim, wherein the porous solid has a solids content of 30-90% w / w at the equilibrium water content (EWC) of the porous solid.
5. The method of any of claims 1 to 4, wherein the polymer mixture exits the die and passes into a bath at a temperature of 25°C or less to remove solvent from the mixture.
6. The method of any one of claims 1 to 5, wherein the porous solid comprises at least one lumen.
7. The method of any of claims 1 to 6, wherein the at least one water soluble polymer comprises a blend of PVA and polyacrylic acid (PAA).
8. 8. The method of any of claims 1 to 7, further comprising passing a core through the die as the polymer mixture passes through the die to extrude the polymer mixture through the die as a tube, and the porous solid is formed around the core.
9. The method of claim 8 , wherein the core is tubular, liquid or gas.
10. The method of any of claims 1 to 9, further comprising a radiopaque agent in the polymer mixture.
11. The method of any of claims 1 to 10, further comprising further removing the solvent by exposing the porous solid to a solvent removal environment for at least 1 hour.
12. The method of any of claims 1 to 11, further comprising annealing said porous solid at a temperature below the melting point of at least one water-soluble polymer in said solvent.
13. The method of any of claims 1 to 12, wherein the porous solid has a lumen and an aspect ratio of at least 10:
1.
14. 1. A catheter comprising a polymeric material, comprising a hydrophilic porous solid tube comprising at least one water soluble polymer forming a hydrophilic porous solid tube, the porous solid tube has a solids content of 30-90% w / w and a Young's modulus of 5-100 MPa at equilibrium water content (EWC); the porous solid tubes do not contain covalent crosslinks between the polymers forming the porous solid tubes; The catheter, wherein the at least one water soluble polymer is selected from polyvinyl alcohol (PVA), blends of PVA and polyethylene glycol (PEG), and blends of PVA and polyacrylic acid (PAA).
15. 15. The catheter of claim 14, wherein the hydrophilic porous solid tube is a hydrophilic nanoporous solid, the pores of which have a size of 100 nm or less.
16. 16. The catheter of claim 14 or 15, having an aspect ratio of at least 10:
1.
17. 17. The catheter of any of claims 14 to 16, wherein the porous solid comprises the at least one water soluble polymer, and at least 50% w / w of the at least one water soluble polymer is poly(vinyl alcohol) (PVA).
18. A catheter according to any one of claims 14 to 17, wherein the porous solid has a solids content of 50-90% w / w at the equilibrium water content (EWC) of the porous solid.
19. The catheter of any of claims 14 to 18, wherein the porous solid comprises at least one water soluble polymer comprising a blend of PVA and polyacrylic acid.
20. The catheter of any one of claims 14 to 19, further comprising a layer of a second material in contact with the porous solid.
21. The catheter of any one of claims 14 to 20, further comprising a second material in the porous solid or a coating of a hydrophobic material on the porous solid.
22. 22. The catheter of claim 21, wherein the second material is at least a portion of a reinforcement material, a fiber, a wire, a braid material, a braided wire, a braided plastic fiber, or a connector.
23. The catheter of any one of claims 14 to 21, further comprising a radiopaque agent.
24. a hydrophilic porous solid tube formed by physically crosslinking at least one water soluble polymer to form a hydrophilic porous solid tube; the hydrophilic porous solid tubes each containing pores having a diameter of 1 μm or less; the hydrophilic porous solid tube has a solids content of 30-90% w / w and a Young's modulus of 5-100 MPa at the equilibrium water content (EWC) of the solid; the hydrophilic porous solid tube does not contain covalent crosslinks between at least one water-soluble polymer forming the hydrophilic porous solid tube; The catheter, wherein the at least one water soluble polymer is selected from polyvinyl alcohol (PVA), blends of PVA and polyethylene glycol (PEG), and blends of PVA and polyacrylic acid (PAA).
25. 25. The catheter of claim 24, wherein the solid is a hydrophilic nanoporous solid, the pores of which have a size of 100 nm or less.
26. 26. The catheter of claim 24 or 25, wherein the at least one water soluble polymer is at least 50% w / w poly(vinyl alcohol) (PVA).
27. 26. The catheter of claim 24 or 25, comprising a lumen, which is a central venous catheter, a peripherally inserted central catheter (PICC), a tunneled catheter, a dialysis catheter, a central venous catheter, a peripheral central catheter, a midline catheter, a peripheral catheter, a tunneled catheter, a dialysis access catheter, a urinary catheter, a neurocatheter, an intraperitoneal catheter, an intra-aortic balloon pump catheter, a diagnostic catheter, an interventional catheter, or a drug delivery catheter.
28. The catheter of any one of claims 24 to 27, further comprising a connector or extension attached to the catheter.
Citation Information
Patent Citations
Polyvinyl alcohol membrane of selective permeability and its production
JP1977123385A
Preparation of tape for treating dermatopathia
JP1980106162A
Permeable membrane
JP1983014906A
Porous transparent polyvinyl alcohol gel and production thereof
JP1986252261A
Elongated article having hollow center core and its production
JP1993261838A